Ultraviolet curable resin composition, method for producing light emitting device, and light emitting device

By controlling the viscosity and glass transition temperature of the UV-curable resin composition, the problems of satellite droplets and insufficient heat resistance in inkjet coating are solved, achieving high-precision and heat-resistant sealing material molding suitable for light-emitting devices.

CN112237050BActive Publication Date: 2025-01-10PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN201980036530.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-27
Filing Date
2019-05-28
Publication Date
2025-01-10
Estimated Expiration
2039-05-28

AI Technical Summary

Technical Problem

In the prior art, UV-curable resin compositions are prone to generating satellite droplets when ejected by inkjet printing, and the heat resistance of the cured product is insufficient, making it difficult to meet the high precision and heat resistance requirements of light-emitting devices.

Method used

A UV-curable resin composition was developed, the maximum peak value of its apparent elongation viscosity-Hencky strain curve at 25°C is below 350 mPa·s, the ratio of the maximum peak value to the viscosity at 25°C is below 20, and it is cured to form a cured product with a glass transition temperature above 80°C, which is suitable for inkjet coating.

Benefits of technology

It effectively avoids the generation of satellite droplets, achieves high-precision sealing material forming, and provides good heat resistance, ensuring that the light-emitting device is not easily degraded under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112237050B_ABST
    Figure CN112237050B_ABST
Patent Text Reader

Abstract

The present disclosure provides a UV-curable resin composition that can be used to produce a cured product that is not prone to satellite droplets when ejected by an inkjet method and has heat resistance. The maximum peak value of the apparent elongation viscosity-Hencky strain curve of the UV-curable resin composition at 25°C is less than 350 mPa·s. The ratio of the maximum peak value of the UV-curable resin composition to the viscosity at 25°C is less than 20. The UV-curable resin composition has the property of becoming a cured product having a glass transition temperature of more than 80°C by curing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an ultraviolet curable resin composition, a method for producing a light-emitting device, and a light-emitting device. Specifically, it relates to an ultraviolet curable resin composition suitable for use in producing a sealing material in a light-emitting device, a method for producing a light-emitting device using the ultraviolet curable resin composition, and a light-emitting device having the sealing material. Background Art

[0002] Patent Document 1 discloses a barrier composite material including a polymerizable compound such as an acrylic resin and a uniform dispersion of surface-functionalized nano zeolite as a composite material for protecting a device that is sensitive to the penetration of H 2 O from the external environment.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 5581332 Summary of the invention

[0006] The present invention aims to provide an ultraviolet curable resin composition, a method for producing a light-emitting device using the ultraviolet curable resin composition, and a light-emitting device having a sealing material made of the ultraviolet curable resin composition, wherein the ultraviolet curable resin composition can produce a cured product that is not prone to generating satellite droplets when ejected by an inkjet method and has heat resistance.

[0007] The maximum peak value of the apparent elongation viscosity-Hencky strain curve at 25°C of the ultraviolet curable resin composition of one embodiment of the present invention is 350 mPa·s or less. The ratio of the maximum peak value of the ultraviolet curable resin composition to the viscosity at 25°C is 20 or less. The ultraviolet curable resin composition has the property of becoming a cured product having a glass transition temperature of 80°C or more by curing.

[0008] A method for manufacturing a light-emitting device according to one embodiment of the present invention is a method for manufacturing a light-emitting device having a light-emitting element and a sealing material covering the light-emitting element. The manufacturing method comprises: forming the ultraviolet curable resin composition by an inkjet method, irradiating the ultraviolet curable resin composition with ultraviolet rays to cure it, thereby manufacturing the sealing material.

[0009] A light-emitting device according to one embodiment of the present invention includes a light-emitting element and a sealing material covering the light-emitting element, wherein the sealing material is formed of a cured product of the ultraviolet curable resin composition. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 This is a cross-sectional view schematically showing a first example of an organic EL light-emitting device in one embodiment of the present invention.

[0011] Figure 2 This is a cross-sectional view schematically showing a second example of the organic EL light-emitting device in one embodiment of the present invention.

[0012] Figure 3 This is a graph showing the apparent elongational viscosity-Hencky strain curve of the composition of Example 1.

[0013] Figure 4 This is a graph showing the apparent elongational viscosity-Hencky strain curve of the composition of Comparative Example 1. DETAILED DESCRIPTION

[0014] First, the outline of the process by which the inventors arrived at the present invention will be described.

[0015] Light-emitting devices including light-emitting elements, such as organic EL light-emitting devices, are used for lighting purposes, display purposes, and the like, and are expected to become more popular in the future.

[0016] Among light-emitting devices, a light-emitting device called a top-emitting type is, for example, configured by arranging a light-emitting element on a supporting substrate, arranging a transparent substrate in a manner opposite to the supporting substrate, and filling a transparent sealing material between the supporting substrate and the transparent substrate. In this case, light emitted by the light-emitting element can be emitted to the outside through the sealing material and the transparent substrate.

[0017] In particular, when the light-emitting element includes an organic EL element, the sealing material inhibits the intrusion of moisture into the organic EL element, thereby inhibiting the generation and growth of dark spots in the organic EL element. Dark spots are non-luminous portions of the organic EL element caused by moisture degradation.

[0018] The sealing material is made of a material containing an organic resin selected from epoxy resin or acrylic resin and a nano zeolite with functionalized surface. In particular, when acrylic resin is used, the sealing material can be made by curing the material by ultraviolet irradiation, etc., so the sealing material can be made without applying a heat load to the light emitting element.

[0019] Sealing materials used for light-emitting elements are required to have high dimensional accuracy. If a composition for producing a sealing material is ejected and molded by an inkjet method, it is expected that a sealing material with high dimensional accuracy can be produced.

[0020] However, when droplets are ejected by the inkjet method, defective droplets called satellite droplets may be generated. Satellite droplets are droplets that separate from the original droplets and adhere to a position in the coating object that is different from the original attachment position of the droplets. If satellite droplets are generated, the dimensional accuracy of the sealing material is deteriorated.

[0021] When the sealing material is made by inkjet method, as the sealing material is thinned, the amount of droplets ejected by inkjet method must be reduced sometimes. In this case, satellite drops are particularly easy to be generated. If the composition is heated to make it low viscosity and then ejected by inkjet method, satellite drops are sometimes suppressed, but by heating, the components in the composition become easy to volatilize, so the composition of the composition is easy to change.

[0022] Furthermore, since the sealing material may be heated during the manufacturing process of the light-emitting device or when the light-emitting device is used, heat resistance is required to prevent the sealing material from being easily degraded by heat.

[0023] Therefore, the inventors have conducted intensive studies to realize an ultraviolet curable resin composition that can produce a cured product that is less likely to generate satellite droplets when ejected by an inkjet method and has heat resistance, and have completed the present invention.

[0024] Hereinafter, one embodiment of the present invention will be described.

[0025] The maximum peak value (hereinafter, sometimes referred to as the maximum peak value) of the apparent elongation viscosity-Hencky strain curve at 25°C of the ultraviolet curable resin composition of the present embodiment (hereinafter, also referred to as composition (X)) is 350 mPa·s or less. In addition, the ratio of the maximum peak value of the composition (X) to the viscosity at 25°C is 20 or less. In addition, the composition (X) has the property of becoming a cured product having a glass transition temperature of 80°C or more by curing.

[0026] The apparent elongation viscosity-Hencky strain curve at 25°C (hereinafter, also referred to as the characteristic curve) is a curve on a graph with the horizontal axis being the Hencky strain and the vertical axis being the apparent elongation viscosity. In order to obtain the characteristic curve, for example, a diameter-time curve at 25°C of the composition (X) is first obtained using a capillary rupture mode elongation strain type rheometer. The characteristic curve can be obtained by performing data conversion on the diameter-time curve at 25°C. As a capillary rupture mode elongation strain type rheometer, for example, a model CaBER 1 manufactured by Thermo Fisher Scientific Co., Ltd. can be used.

[0027] In order to obtain a diameter-time curve at 25°C using a capillary rupture elongation strain rheometer, a liquid sample is arranged between the upper plate and the lower plate in the capillary rupture elongation strain rheometer. In this state, the upper plate is pulled relative to the lower plate. The diameter of the sample that changes during the pulling of the upper plate is continuously measured with a laser micrometer. The test conditions are: the diameter of the upper plate and the lower plate is 4mm, the initial gap between the upper plate and the lower plate is 1mm, the pulling distance (displacement) of the upper plate is 3mm, the pulling time of the upper plate is 30 milliseconds, and the diameter measurement rate is 30000Hz (30,000 times / second). The measurement results of the diameter of the obtained sample are plotted into a graph with the elapsed time from the start of the pulling of the upper plate as the horizontal axis and the diameter of the sample as the vertical axis, thereby obtaining a diameter-time curve at 25°C.

[0028] In order to determine the maximum peak value of the characteristic curve of the composition (X), the sample of the composition (X) is measured three times to obtain three characteristic curves. The maximum peak value of each of the three characteristic curves is calculated. The average value of the three peak values ​​obtained is calculated. The average value is taken as the maximum peak value of the characteristic curve of the composition (X).

[0029] On the other hand, the viscosity of the composition (X) at 25° C. was measured by using a rheometer at a shear rate of 100 s -1 As a rheometer, for example, DHR-2 manufactured by Anton Paar Japan can be used.

[0030] Since the maximum peak value of the composition (X) is 350 mPa·s or less and the ratio of the maximum peak value to the viscosity at 25° C. is 20 or less, when the composition (X) is applied by an inkjet method, undesirable droplets called satellite droplets are less likely to be generated. The reason why satellite droplets are less likely to be generated is presumed to be as follows.

[0031] The maximum peak value of the characteristic curve reflects the behavior of the composition (X) in the strain solidification region (shrinkage reduction region) when the composition (X) is stretched, and the high maximum peak value means that the degree of difficulty in deformation is high when the composition (X) is stretched. In the case of applying ink by inkjet method, the droplets of ink fall from the nozzle in a trailing manner. That is, a spherical part and a tail-shaped part from the spherical part toward the nozzle are generated in the droplet. If the degree of elasticity increase generated during the elongation of the tail-shaped part becomes larger and becomes difficult to deform, the tail-shaped part is difficult to leave from the nozzle, so the droplet is easily separated into a spherical part and a tail-shaped part. Therefore, the tail-shaped part is easy to become a satellite drop. In the case of a high maximum peak value of the characteristic curve, especially when the ratio of the maximum peak value to the viscosity is large, the degree of difficulty in deformation generated in the tail-shaped part of the droplet becomes larger, and therefore, it is considered that satellite drops are easily generated.

[0032] However, in the present embodiment, since the maximum peak is 350 mPa·s or less, and the ratio of the maximum peak to the viscosity at 25° C. is 20 or less, it is considered that the tail-shaped portion of the droplet of the composition (X) is easily deformed even in the strain solidification region. Therefore, the tail-shaped portion is easy to leave the nozzle quickly, and the tail-shaped portion is easily absorbed by the spherical portion. Therefore, the droplets are not easy to separate. As a result, it is considered that satellite droplets are not easy to be generated.

[0033] In addition, if the tail-shaped portion is easily absorbed by the spherical portion, even if the speed of the droplets of the composition (X) is increased when the droplets are ejected by the inkjet method, the tail-shaped portion is easily absorbed by the spherical portion before the droplets reach the object. Therefore, by increasing the speed of the droplets, the trajectory of the droplets can be made less susceptible to external interference, thereby allowing the composition (X) to be precisely applied by the inkjet method.

[0034] In addition, when the droplets of the composition (X) are ejected from the nozzle, the tail-shaped portion is easily deformed, so the tail-shaped portion is easily and quickly separated from the nozzle. That is, the droplets are easily and quickly separated from the nozzle. Therefore, even if the composition (X) is not heated, the composition (X) can be easily applied by the inkjet method.

[0035] In addition, since the composition (X) has the property of becoming a cured product having a glass transition temperature of 80°C or higher by curing, the cured product can have good heat resistance. Therefore, for example, when the cured product is subjected to a treatment accompanied by a temperature rise, the cured product is not easily deteriorated. The composition (X) is more preferably a cured product having a glass transition temperature of 90°C or higher by curing, and is further preferably a cured product having a glass transition temperature of 100°C or higher.

[0036] Therefore, in the present embodiment, defects are less likely to occur when the composition (X) is applied by an inkjet method, and a cured product having excellent heat resistance can be produced from the composition (X).

[0037] It is preferred that the sealing material covering the organic EL element in the organic EL light-emitting device is made from the composition (X). That is, it is preferred that the sealing material covering the organic EL element in the organic EL light-emitting device is formed by a cured product of the composition (X). In this case, when making the sealing material, even if the composition (X) is applied by an inkjet method, satellite drops are not easily produced, so the sealing material can be made with high precision. In addition, since the sealing material has good heat resistance, the sealing material is not easy to deteriorate over time, and even if the sealing material is subjected to a treatment accompanied by a temperature rise during the manufacture of the organic EL light-emitting device, the sealing material is not easy to deteriorate. It should be noted that EL is an abbreviation for electroluminescence. In addition, the organic EL element is also referred to as an organic light-emitting diode.

[0038] The maximum peak value of the composition (X), the ratio of the maximum peak value to the viscosity at 25° C., and the glass transition temperature of the cured product can be achieved by the composition of the composition (X) described in detail below.

[0039] It should be noted that in the present embodiment, the maximum peak value must be reduced to less than 350 mPa·s, and the viscosity at 25°C must be reduced relative to the maximum peak value in such a manner that the ratio of the maximum peak value to the viscosity at 25°C is less than 20. Therefore, it is difficult to generally specify the conditions of the composition of the composition (X). However, the inventors have found several methods for reducing the maximum peak value and several methods for reducing the viscosity as described below, and by appropriately combining these methods, it is possible to achieve a maximum peak value of less than 350 mPa·s and a ratio of the maximum peak value to the viscosity at 25°C of less than 20. Examples of specific compositions are shown in the Examples column described later.

[0040] The viscosity of the composition (X) at 25°C is preferably 1 mPa·s or more and 30 mPa·s or less. In this case, the composition (X) can be formed by applying the composition (X) at room temperature by a casting method, an inkjet method, etc. In particular, if the viscosity is 30 mPa·s or less, when the composition (X) is applied by an inkjet method, the ejection speed of the composition (X) from the nozzle is not easy to decrease, and satellite drops are particularly difficult to generate. The viscosity is more preferably 20 mPa·s or less, and further preferably 15 mPa·s or less. The viscosity is also preferably 5 mPa·s or more.

[0041] The viscosity of the composition (X) at 40°C is also preferably 1 mPa·s or more and 30 mPa·s or less. In this case, no matter what the viscosity of the composition (X) at room temperature is, as long as the composition (X) is slightly heated, it can be made low-viscosity. Therefore, if heated, the composition (X) can be easily formed by a method such as a casting method, or the composition (X) can be formed by an inkjet method. In addition, since the viscosity of the composition (X) can be made low without substantially heating the composition (X), it is not easy to cause changes in the composition of the composition (X) caused by the volatilization of the components in the composition (X). The viscosity is more preferably less than 20 mPa·s, and more preferably less than 15 mPa·s. The viscosity is also preferably more than 5 mPa·s.

[0042] Such a low viscosity of the composition (X) at 25° C. or 40° C. can also be achieved by the composition of the composition (X) described in detail below.

[0043] The total light transmittance of the cured product of the composition (X) is preferably 90% or more when the thickness dimension is 10 μm. In this case, if the cured product is applied to the sealing material 5 in the light-emitting device 1, the extraction efficiency of the light emitted to the outside through the sealing material 5 can be particularly improved. The light transmittance of such a cured product can also be achieved by the composition of the composition (X) described in detail below.

[0044] It is also preferred that the surface tension of the composition (X) is more than 20mN / cm and less than 40mN / cm. In this case, when the composition (X) is applied by an inkjet method, it is more difficult to produce satellite drops. It is believed that this is because, if the surface tension is more than 20mN / cm, when the droplets of the composition (X) are separated from the nozzle, it is difficult to produce a tail-shaped part in the droplet, and if the surface tension is less than 40mN / cm, the droplets of the composition (X) are particularly easy to separate from the nozzle. The surface tension is more preferably more than 30mN / cm and less than 40mN / cm, and more preferably more than 31mN / cm and less than 38mN / cm. The surface tension of such a composition (X) can also be achieved by the composition of the composition (X) described in detail below.

[0045] Hereinafter, this embodiment will be described in more detail.

[0046] 1. Structure of the light-emitting device

[0047] First, the structure of the light emitting device 1 is described. The light emitting device 1 includes a light emitting element 4 and a sealing material 5 covering the light emitting element 4. The sealing material 5 may cover the light emitting element 4 in a state of being in direct contact with the light emitting element 4, or may cover the light emitting element 4 in a state of being sandwiched between the sealing material 5 and the light emitting element 4. The light emitting device 1 may be, for example, a lighting device or a display device (display).

[0048] The light emitting element 4 includes, for example, a light emitting diode. The light emitting diode includes, for example, at least one of an organic EL element (organic light emitting diode) and a micro light emitting diode. When the light emitting element 4 includes an organic light emitting diode, the light emitting device 1 including the light emitting element 4 is, for example, an organic EL display. When the light emitting element 4 includes a micro light emitting diode, the light emitting device 1 including the light emitting element 4 is, for example, a micro LED display. It should be noted that EL refers to electroluminescence and LED refers to a light emitting diode.

[0049] Reference Figure 1A first example of the structure of the light emitting device 1 is described. The light emitting device 1 is a top emission type. The light emitting device 1 includes a supporting substrate 2, a transparent substrate 3 opposed to the supporting substrate 2 with a gap therebetween, a light emitting element 4 located on the surface of the supporting substrate 2 opposed to the transparent substrate 3, and a sealing material 5 filled between the supporting substrate 2 and the transparent substrate 3. In addition, in the first example, the light emitting device 1 includes a passivation layer 6 covering the surface of the supporting substrate 2 opposed to the transparent substrate 3 and the light emitting element 4. That is, the passivation layer 6 is interposed between the light emitting element 4 and the sealing material 5 covering the light emitting element 4.

[0050] The supporting substrate 2 is made of, for example, a resin material, but is not limited thereto. The transparent substrate 3 is made of a light-transmitting material. The transparent substrate 3 is, for example, a glass substrate or a transparent resin substrate. When the light-emitting element 4 includes an organic EL element, the organic EL element includes, for example, a pair of electrodes and an organic light-emitting layer located between the electrodes. The organic light-emitting layer includes, for example, a hole injection layer, a hole transport layer, an organic light-emitting layer, and an electron transport layer, and these layers are stacked in the above order. Figure 1 Only one light emitting element 4 is shown in the figure, but the light emitting device 1 may also include a plurality of light emitting elements 4, and the plurality of light emitting elements 4 form an array on the supporting substrate 2. The passivation layer 6 is preferably made of silicon nitride or silicon oxide.

[0051] Reference Figure 2 A second example of the structure of the light emitting device 1 is described. Figure 1 The common elements of the first example shown are Figure 2 Marked with Figure 1 The same symbols are used and detailed descriptions are appropriately omitted. Figure 2 The light emitting device 1 shown is also a top emission type and includes a supporting substrate 2, a transparent substrate 3 spaced apart from the supporting substrate 2, a light emitting element 4 located on the surface of the supporting substrate 2 facing the transparent substrate 3, and a sealing material 5 covering the light emitting element 4.

[0052] When the light emitting element 4 includes an organic EL element, the organic EL element is the same as in the first example, and includes, for example, a pair of electrodes 41 and 43 and an organic light emitting layer 42 located between the electrodes 41 and 43. The organic light emitting layer 42 includes, for example, a hole injection layer 421, a hole transport layer 422, an organic light emitting layer 423, and an electron transport layer 424, and these layers are stacked in the above order.

[0053] The light-emitting device 1 includes a plurality of light-emitting elements 4, and the plurality of light-emitting elements 4 form an array 9 (hereinafter referred to as the element array 9) on the supporting substrate 2. The element array 9 also includes a partition wall 7. The partition wall 7 is located on the supporting substrate 2 and separates two adjacent light-emitting elements 4. The partition wall 7 is made, for example, by forming a photosensitive resin material using a photolithography method. The element array 9 also includes a connection wiring 8 that electrically connects the electrodes 43 and the electron transport layer 424 of the adjacent light-emitting elements 4 to each other. The connection wiring 8 is provided on the partition wall 7.

[0054] The light emitting device 1 further includes a passivation layer 6 covering the light emitting element 4. The passivation layer 6 is preferably made of silicon nitride or silicon oxide. The passivation layer 6 includes a first passivation layer 61 and a second passivation layer 62. The first passivation layer 61 covers the light emitting element 4 by covering the element array 9 in a state of direct contact with the element array 9. The second passivation layer 62 is arranged at a position opposite to the element array 9 relative to the first passivation layer 61, and a gap is formed between the second passivation layer 62 and the first passivation layer 61. The sealing material 5 is filled between the first passivation layer 61 and the second passivation layer 62. That is, the first passivation layer 61 is between the light emitting element 4 and the sealing material 5 covering the light emitting element 4.

[0055] In addition, a second sealing material 52 is filled between the second passivation layer 62 and the transparent substrate 3. The second sealing material 52 is made of, for example, a transparent resin material. There is no particular limitation on the material of the second sealing material 52. The material of the second sealing material 52 can be the same as that of the sealing material 5 or different.

[0056] The sealing material 5 in the light emitting device 1 having the above-exemplified structure can be produced from the ultraviolet curable resin composition of this embodiment. That is, the ultraviolet curable resin composition is used to produce the sealing material 5 for the light emitting element 4. In other words, the ultraviolet curable resin composition is preferably a composition for producing a sealing material, a composition for sealing a light emitting element, or a composition for producing a light emitting device.

[0057] 2. Ultraviolet curable resin composition

[0058] The ultraviolet curable resin composition (hereinafter, also referred to as composition (X)) will be described.

[0059] The composition (X) contains a curable component having ultraviolet curability. The curable component contains, for example, a cationically polymerizable compound (F) and a cationic curing catalyst (G). The curable component may contain a radically polymerizable compound and a photoradical polymerization initiator (B).

[0060] When the curable component contains a radical polymerizable compound and a photoradical polymerization initiator (B), the radical polymerizable compound preferably contains an acrylic compound (A). In this case, when the composition (X) is irradiated with ultraviolet rays, a photoradical polymerization reaction is initiated by the photoradical polymerization initiator (B), and the acrylic compound (A) is cured, thereby being able to produce a cured product.

[0061] The components of the composition (X) (hereinafter also referred to as composition (X1)) containing the acrylic compound (A) and the photoradical polymerization initiator (B) will be described in more detail.

[0062] As described above, the composition (X1) contains an acrylic compound (A). The acrylic compound (A) has one or more (meth)acryloyl groups in one molecule.

[0063] The viscosity of the acrylic compound (A) as a whole at 25°C is preferably 50 mPa·s or less. In this case, the acrylic compound (A) can make the composition (X1) particularly low in viscosity. The viscosity of the acrylic compound (A) as a whole is further preferably 30 mPa·s or less, and particularly preferably 20 mPa·s or less. In addition, the viscosity of the acrylic compound (A) as a whole is, for example, 3 mPa·s or more.

[0064] The viscosity of the acrylic compound (A) as a whole at 40°C is also preferably 50 mPa·s or less. In this case, the acrylic compound (A) can make the composition (X1) particularly low in viscosity when heated. The viscosity of the acrylic compound (A) as a whole is further preferably 30 mPa·s or less, and particularly preferably 20 mPa·s or less. In addition, the viscosity of the acrylic compound (A) as a whole is, for example, 3 mPa·s or more.

[0065] The compounds that may be contained in the acrylic compound (A) are described.

[0066] The acrylic compound (A) preferably contains a multifunctional acrylic compound (A1) having two or more (meth)acryloyl groups in one molecule. In this case, the multifunctional acrylic compound (A1) can increase the glass transition temperature of the cured product, thereby improving the heat resistance of the cured product and the sealing material 5. Preferably, the amount of the multifunctional acrylic compound (A1) is 50% by mass or more and 100% by mass or less relative to the total amount of the acrylic compound (A). The acrylic compound (A) may contain only the multifunctional acrylic compound (A1).

[0067] The polyfunctional acrylic compound (A1) contains, for example, 1,3-butanediol di(meth)acrylate, 1,4-butanediol oligoacrylate, diethylene glycol diacrylate, 1,6-hexanediol oligoacrylate, neopentyl glycol diacrylate, triethylene glycol diacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, cyclohexanedimethanol diacrylate, tricyclodecane dimethanol diacrylate, bisphenol A polyethoxy diacrylate, bisphenol F polyethoxy diacrylate, pentaerythritol tetraacrylate, propoxylated neopentyl glycol diacrylate, trimethylolpropane triacrylate, tri(2) -hydroxyethyl) isocyanurate triacrylate, pentaerythritol triacrylate, ethoxylated (3) trimethylolpropane triacrylate, propoxylated (3) glycerol triacrylate, pentaerythritol tetraacrylate, ditrimethylolpropane tetraacrylate, ethoxylated (4) pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, 2-(2-ethoxyethoxy)ethyl acrylate, hexanediol diacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, tripropylene glycol triacrylate, dipentaerythritol hexaacrylate, ethylene glycol diacrylate, 1,6-hexanediol diacrylate, ethoxylated 1, 6-Hexanediol diacrylate, polypropylene glycol diacrylate, 1,4-butanediol diacrylate, 1,9-nonanediol diacrylate, tetraethylene glycol diacrylate, 2-n-butyl-2-ethyl-1,3-propanediol diacrylate, hydroxypivalic acid neopentyl glycol diacrylate, hydroxypivalic acid trimethylolpropane triacrylate, ethoxylated phosphoric acid triacrylate, ethoxylated tripropylene glycol diacrylate, neopentyl glycol modified trimethylolpropane diacrylate, stearic acid modified pentaerythritol diacrylate, tetramethylolpropane triacrylate, tetramethylolmethane triacrylate, caprolactone modified trimethylolpropane triacrylate. At least one compound selected from the group consisting of acrylate, propoxylated glycerol triacrylate, tetramethylolmethane tetraacrylate, ethoxylated pentaerythritol tetraacrylate, dipentaerythritol hexaacrylate, caprolactone-modified dipentaerythritol hexaacrylate, dipentaerythritol hydroxypentaacrylate, neopentyl glycol oligoacrylate, trimethylolpropane oligoacrylate, pentaerythritol oligoacrylate, ethoxylated neopentyl glycol di(meth)acrylate, propoxylated neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, ethoxylated trimethylolpropane triacrylate, and propoxylated trimethylolpropane triacrylate.

[0068] The acrylic acid equivalent of the polyfunctional acrylic compound (A1) is preferably 150 g / eq or less, more preferably 90 g / eq or more and 150 g / eq or less. The weight average molecular weight of the polyfunctional acrylic compound (A1) is, for example, 100 or more and 1000 or less, more preferably 200 or more and 800 or less.

[0069] It is preferred that the multifunctional acrylic compound (A1) has at least one of a benzene ring, an alicyclic ring and a polar group. The polar group is, for example, at least one of an OH group and an NHCO group. In this case, the shrinkage of the composition (X1) during curing can be particularly reduced. In addition, the adhesion between the cured product and inorganic compounds such as silicon nitride and silicon oxide can also be improved. The multifunctional acrylic compound (A1) particularly preferably contains at least one compound selected from tricyclodecane dimethanol diacrylate, bisphenol A polyethoxy diacrylate, bisphenol F polyethoxy diacrylate, trimethylolpropane triacrylate and pentaerythritol tetraacrylate. These compounds can particularly reduce the shrinkage of the composition (X1) during curing. In addition, these compounds can also improve the adhesion between the cured product and inorganic compounds such as silicon nitride and silicon oxide.

[0070] It is also preferred that the polyfunctional acrylic compound (A1) contains a compound (A11) having a structure represented by the following formula (40).

[0071] CH2=CR 1 -COO-(R 3 -O) n -CO-CR 2 =CH2 (40)

[0072] In formula (40), R 1 and R 2 are each hydrogen or methyl, n is an integer greater than 1, R 3 is an alkylene group having 3 or more carbon atoms. When n is 2 or more, a plurality of R 3 They can be the same or different.

[0073] The compound (A11) has a structure represented by the formula (40), and in particular R 3 The number of carbon atoms in the sealing material 5 is 3 or more, so it is difficult to improve the affinity of the sealing material 5 with water. Therefore, the light emitting element 4 is not easily degraded by water. 3 The number of carbon atoms is, for example, 3 or more and 15 or less. In addition, since the compound (A11) has a structure represented by the formula (40), especially having two (meth)acryloyl groups in one molecule, the glass transition temperature of the cured product can be increased, thereby improving the heat resistance of the cured product and the sealing material 5. In addition, n in the formula (40) is, for example, an integer of 1 or more and 12 or less.

[0074] The percentage of the compound (A11) relative to the acrylic compound (A) is preferably 50% by mass or more. In this case, the affinity of the cured product and the sealing material 5 for water is particularly unlikely to become high. The percentage of the compound (A11) relative to the acrylic compound (A) is, for example, 100% by mass or less, or 95% by mass or less, preferably 80% by mass or less.

[0075] It is particularly preferred that the compound (A11) contains a compound (A12) having a boiling point of 270°C or more. That is, it is preferred that the acrylic compound (A) contains a compound (A12) having a structure shown in formula (40) and a boiling point of 270°C or more. In this case, the acrylic compound (A) is not easy to volatilize from the composition (X) during storage of the composition (X) and when the composition (X) is heated. Therefore, the storage stability of the composition (X) is not easily impaired. In addition, even if the compound (A12) does not react and remains in the cured product of the composition (X) and the sealing material 5, it is not easy to generate outgassing caused by the compound (A12) from the cured product and the sealing material 5. Therefore, it is not easy to generate gaps caused by outgassing in the light-emitting device 1. If there are gaps in the light-emitting device 1, moisture may penetrate into the light-emitting element 4 through the gaps, and if it is not easy to generate gaps, it is not easy for moisture to penetrate into the light-emitting element 4. The boiling point is the boiling point at normal pressure obtained by converting the boiling point at reduced pressure, and can be determined, for example, by the method described in Science of Petroleum, Vol. II. P. 1281 (1938). The boiling point of compound (A12) is more preferably 280° C. or higher.

[0076] The percentage of the compound (A12) relative to the acrylic compound (A) is preferably 50% by mass or more. In this case, the storage stability of the composition (X) can be effectively improved, and the generation of outgassing from the sealing material 5 can be effectively reduced, and the affinity of the sealing material 5 for water is particularly unlikely to increase. The percentage of the compound (A12) relative to the acrylic compound (A) is, for example, 100% by mass or less, or 95% by mass or less, and preferably 80% by mass or less.

[0077] The viscosity of the compound (A12) at 25°C is preferably 25 mPa·s or less. In this case, the compound (A12) can reduce the viscosity of the composition (X). The viscosity of the compound (A12) at 25°C is more preferably 25 mPa·s or less, further preferably 20 mPa·s or less, and particularly preferably 15 mPa·s or less. In addition, the viscosity of the compound (A12) at 25°C is, for example, 1 mPa·s or more, preferably 3 mPa·s or more, and further preferably 5 mPa·s or more.

[0078] The compound (A12) contains, for example, at least one compound selected from the group consisting of alkylene glycol di(meth)acrylates, polyalkylene glycol di(meth)acrylates, and alkylene oxide-modified alkylene glycol di(meth)acrylates.

[0079] The di(meth)acrylate of alkylene glycol is a compound wherein n is 1 in the formula (40). In this case, R 3 The number of carbon atoms in R is preferably 4 to 12. 3It may be straight chain or branched. In particular, the di(meth)acrylate of alkylene glycol preferably contains at least one compound selected from 1,4-butanediol diacrylate, 1,3-butanediol diacrylate, neopentyl glycol diacrylate, 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, 1,10-decanediol diacrylate, 1,4-butanediol dimethacrylate, 1,3-butanediol dimethacrylate, neopentyl glycol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, 1,10-decanediol dimethacrylate, and 1,12-dodecanediol dimethacrylate. The di(meth)acrylate of alkylene glycol preferably contains a product selected from the group consisting of SR213 manufactured by Sartomer, V195 manufactured by Osaka Organic Chemical Industry Co., Ltd., SR212 manufactured by Sartomer, SR247 manufactured by Sartomer, LIGHT ACRYLATE manufactured by Kyoei Chemical Industry Co., Ltd. NP-A, product number SR238NS manufactured by Sartomer, product number V230 manufactured by Osaka Organic Chemical Industry Co., Ltd., product number HDDA manufactured by Daicel, product number 1,6HX-A manufactured by Kyoei Chemical Industry Co., Ltd., product number V260 manufactured by Osaka Organic Chemical Industry Co., Ltd., product number 1,9-ND-A manufactured by Kyoei Chemical Industry Co., Ltd., product number A-NOD-A manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product number CD595 manufactured by Sartomer, product number SR214NS manufactured by Sartomer, product number BD manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product number SR297 manufactured by Sartomer, product number SR248 manufactured by Sartomer, product name LIGHT ESTER NP manufactured by Kyoei Chemical Industry Co., Ltd., product number SR239NS manufactured by Sartomer, product name LIGHT ESTER manufactured by Kyoei Chemical Industry Co., Ltd. At least one compound selected from the group consisting of 1,6HX, product number HD-N manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product name LIGHT ESTER 1,9ND manufactured by Kyoei Chemical Industry Co., Ltd., product number NOD-N manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product name LIGHT ESTER 1,10DC manufactured by Kyoei Chemical Industry Co., Ltd., product number DOD-N manufactured by Shin-Nakamura Chemical Industry Co., Ltd., and product number SR262 manufactured by Sartomer.

[0080] The di(meth)acrylate of polyalkylene glycol is a compound wherein n in formula (40) is 2 or more. n is, for example, 2 to 10, preferably 2 to 7, more preferably 2 to 6, and even more preferably 2 to 3. 3The number of carbon atoms is, for example, 2 to 5. The greater the number of carbon atoms, the higher the hydrophobicity of the cured product and the color resist 1, and the less likely it is for water to penetrate the color resist 1. The di(meth)acrylate of the polyalkylene glycol particularly preferably contains at least one compound selected from diethylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, hexaethylene glycol dimethacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, tripropylene glycol dimethacrylate, and tritetramethylene glycol diacrylate. The polyalkylene glycol di(meth)acrylate is particularly preferably selected from the group consisting of product number SR230 manufactured by Sartomer, product number SR508NS manufactured by Sartomer, product number DPGDA manufactured by Daicel, product number SR306NS manufactured by Sartomer, product number TPGDA manufactured by Daicel, product number V310HP manufactured by Osaka Organic Chemical Industry Co., Ltd., product number APG200 manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product name LIGHT ACRYLATE PTMGA-250 manufactured by Kyoei Chemical Industry Co., Ltd., product number SR231NS manufactured by Sartomer, product name LIGHT ESTER 2EG manufactured by Kyoei Chemical Industry Co., Ltd., product number SR205NS manufactured by Sartomer, product name LIGHT ESTER 3EG manufactured by Kyoei Chemical Industry Co., Ltd., product number SR210NS manufactured by Sartomer, product name LIGHT ESTER 5EG manufactured by Kyoei Chemical Industry Co., Ltd. At least one compound selected from the group consisting of 4EG, ACRYESTER HX (product name) manufactured by Mitsubishi Chemical Corporation, and 3PG (product number) manufactured by Shin-Nakamura Chemical Industry Co., Ltd.

[0081] The di(meth)acrylate of alkylene oxide-modified alkylene glycol includes, for example, propylene oxide-modified neopentyl glycol. The di(meth)acrylate of alkylene oxide-modified alkylene glycol includes, for example, EBECRYL145 manufactured by Daicel Corporation.

[0082] It is preferred that the percentage of components having a boiling point of 270°C or higher in the acrylic compound (A) is 80% by mass or higher. When the acrylic compound (A) contains the compound (A12), it is preferred that the percentage of components having a boiling point of 270°C or higher, including the compound (A12), in the acrylic compound (A) is 80% by mass or higher. In this case, the storage stability of the composition (X) is particularly unlikely to be impaired, and it is particularly unlikely that outgassing will occur from the cured product and the sealing material 5. It is further preferred that the percentage of components having a boiling point of 280°C or higher in the acrylic compound (A) is 80% by mass or higher.

[0083] The compound (A11) may contain a compound (A13) other than the compound (A12).

[0084] The multifunctional acrylic compound (A1) may contain a compound (A14) having three or more (meth)acryloyl groups in one molecule. That is, the acrylic compound (A) may contain the compound (A14). In this case, the compound (A14) may contain, for example, at least one selected from trimethylolpropane triacrylate and trimethylolpropane trimethacrylate. If the acrylic compound (A) contains the compound (A14), the compound (A14) can particularly increase the glass transition temperature of the cured product, and therefore, can particularly increase the heat resistance of the cured product and the color resist 1.

[0085] When the acrylic compound (A) includes compound (A14), the percentage of compound (A14) relative to the acrylic compound (A) is preferably greater than 0% by mass and less than 25% by mass. The percentage of compound (A14) is more preferably more than 10% by mass. In this case, the glass transition temperature of the cured product can be particularly improved. In addition, if compound (A14) is less than 25% by mass, the viscosity increase of the composition (X) caused by compound (A14) is not likely to occur. If the percentage of compound (A14) is less than 20% by mass, the viscosity increase of the composition (X) is particularly not likely to occur.

[0086] When the acrylic compound (A) contains a compound (A11) having a structure represented by formula (40), it is preferred that the compound (A11) does not contain a compound in which the value of n in formula (40) is 5 or more. 3 -O) n In the case of a polyethylene glycol skeleton, it is particularly preferred that the compound whose n value in the formula (40) is greater than 5 is not included. Even if the compound (A11) contains a compound whose n value in the formula (40) is greater than 5, it is preferred that the percentage of the compound whose n value in the formula (40) is greater than 5 relative to the acrylic compound (A) is 20% by mass or less. In addition, even if the compound (A11) contains a compound whose n value in the formula (40) is greater than 5, it is preferred that the compound (A11) does not contain a compound whose n value is greater than 9, and further preferably does not contain a compound whose n value is greater than 7. In these cases, the viscosity of the composition (X) is particularly unlikely to increase.

[0087] It is also preferred that the acrylic compound (A) contains a monofunctional acrylic compound (A2) having only one (meth)acryloyl group in one molecule. The monofunctional acrylic compound (A2) can suppress shrinkage of the composition (X1) during curing.

[0088] The amount of the monofunctional acrylic compound (A2) is preferably greater than 0% by mass and less than 50% by mass relative to the total amount of the acrylic compound (A). If the amount of the monofunctional acrylic compound (A2) is greater than 0% by mass, the shrinkage of the composition (X1) during curing can be suppressed. In addition, if the amount of the monofunctional acrylic compound (A2) is less than 50% by mass, the amount of the multifunctional acrylic compound (A1) can be more than 50% by mass, thereby particularly improving the heat resistance of the cured product and the sealing material 5. The amount of the monofunctional acrylic compound (A2) is more preferably more than 5% by mass, and further preferably less than 30% by mass.

[0089] The monofunctional acrylic compound (A2) includes, for example, tetrahydrofurfuryl acrylate, isobornyl acrylate, 2-hydroxyethyl acrylate, 4-hydroxybutyl acrylate, isobutyl acrylate, tert-butyl acrylate, isooctyl acrylate, 2-methoxyethyl acrylate, methoxytriethylene glycol acrylate, 2-ethoxyethyl acrylate, 3-methoxybutyl acrylate, ethoxyethyl acrylate, butoxyethyl acrylate, ethoxydiethylene glycol acrylate, methoxyethyl acrylate ( Metric ethyl acrylate), diethylene glycol monoethyl ether acrylate, cyclic trimethylolpropane formal monoacrylate, imide acrylate, isopentyl acrylate, ethoxylated succinic acid acrylate, trifluoroethyl acrylate, ω-carboxy polycaprolactone monoacrylate, cyclohexyl acrylate, 2-(2-ethoxyethoxy)ethyl acrylate, stearyl acrylate, diethylene glycol monobutyl ether acrylate, lauryl acrylate, isodecyl acrylate, 3,3,5-trimethylcyclohexanol acrylate , isooctyl acrylate, octyl / decyl acrylate, tridecyl acrylate, caprolactone acrylate, ethoxylated (4) nonylphenol acrylate, methoxy polyethylene glycol (350) monoacrylate, methoxy polyethylene glycol (550) monoacrylate, phenoxyethyl acrylate, (meth) cyclohexyl acrylate, (meth) dicyclopentyl acrylate, (meth) tetrahydrofurfuryl acrylate, benzyl acrylate, methylphenoxyethyl acrylate, 4-tert-butylcyclohexyl acrylate, caprolactone modified tetrahydrofurfuryl acrylate, propylene At least one compound selected from the group consisting of tribromophenyl acrylate, ethoxylated tribromophenyl acrylate, 2-phenoxyethyl acrylate, ethylene oxide adduct of 2-phenoxyethyl acrylate, propylene oxide adduct of 2-phenoxyethyl acrylate, acryloyl morpholine, isobornyl acrylate, dicyclopentanyl acrylate, phenoxydiethylene glycol acrylate, 2-hydroxy-3-phenoxypropyl acrylate, 1,4-cyclohexanedimethanol monoacrylate, 3-methacryloyloxymethyloxirane and 3-acryloyloxymethyloxirane.

[0090] The monofunctional acrylic compound (A2) may contain at least one compound selected from the group consisting of a compound having an alicyclic structure and a compound having a cyclic ether structure.

[0091] The compound having an alicyclic structure contains, for example, at least one compound selected from phenoxyethyl acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl acrylate, methylphenoxyethyl acrylate, 4-tert-butylcyclohexyl acrylate, caprolactone-modified tetrahydrofurfuryl acrylate, tribromophenyl acrylate, ethoxylated tribromophenyl acrylate, 2-phenoxyethyl acrylate, ethylene oxide adduct of 2-phenoxyethyl acrylate, propylene oxide adduct of 2-phenoxyethyl acrylate, acryloylmorpholine, isobornyl acrylate, dicyclopentanyl acrylate, phenoxydiethylene glycol acrylate, 2-hydroxy-3-phenoxypropyl acrylate and 1,4-cyclohexanedimethanol monoacrylate.

[0092] The number of ring members of the cyclic ether structure in the compound having a cyclic ether structure is preferably 3 or more, more preferably 3 or more and 4 or less. The number of carbon atoms contained in the cyclic ether structure is preferably 2 or more and 9 or less, more preferably 2 or more and 6 or less. The compound having a cyclic ether structure contains, for example, at least one compound selected from 3-methacryloyloxymethyloxirane and 3-acryloyloxymethyloxirane.

[0093] Preferably, the acrylic compound (A) further contains at least one compound selected from a compound having silicon in its molecular skeleton (A41), a compound having phosphorus in its molecular skeleton (A42), and a compound having nitrogen in its molecular skeleton (A43). In this case, the adhesion between the cured product and the sealing material 5 and the inorganic material component is improved. Therefore, it is not easy to generate a gap between the sealing material 5 and the passivation layer 6, and it is not easy to cause moisture to invade the light-emitting element 4 through the gap.

[0094] It should be noted that compound (A41), compound (A42) and compound (A43) are defined by the types of atoms in the molecular skeleton. Therefore, the compounds included in each of the multifunctional acrylic compound (A1) and the monofunctional acrylic compound (A2) may overlap with the compounds included in each of compound (A41), compound (A42) and compound (A43).

[0095] Compound (A41) contains, for example, at least one compound selected from 3-(trimethoxysilyl)propyl acrylate (e.g., product number KBM5103 manufactured by Shin-Etsu Chemical Co., Ltd.) and (meth)acryloyl group-containing alkoxysilane oligomer (e.g., product number KR-513 manufactured by Shin-Etsu Chemical Co., Ltd.). However, since the boiling point of 3-(trimethoxysilyl)propyl acrylate is 260° C., when the acrylic compound (A) contains 3-(trimethoxysilyl)propyl acrylate, the percentage of 3-(trimethoxysilyl)propyl acrylate relative to the acrylic compound (A) needs to be 10% by mass or less.

[0096] Compound (A42) includes, for example, acidic phosphonooxy (meth)acrylates such as acidic phosphonooxy polyoxypropylene glycol monomethacrylate.

[0097] The compound (A43) contains, for example, at least one compound selected from the group consisting of acryloylmorpholine, diethylacrylamide, dimethylaminopropylacrylamide, and pentamethylpiperidinyl methacrylate.

[0098] When the acrylic compound (A) contains at least one compound selected from the group consisting of compound (A41), compound (A42) and compound (A43), the percentage of the total amount of compound (A41), compound (A42) and compound (A43) relative to the acrylic compound (A) is preferably from 0.5 mass % to 20 mass %, and more preferably from 1 mass % to 15 mass %.

[0099] It is also preferred that the acrylic compound (A) contains a compound having an isobornyl skeleton. In this case, when the size of the droplets of the composition (X) ejected by the inkjet method is reduced, satellite drops can be particularly difficult to produce. That is, it is easy to miniaturize the droplets without producing satellite drops. Therefore, it is easy to form the small droplets of the composition (X) at a high density by the inkjet method, so it is easy to achieve the thinning of the sealing material 5. In the case where the acrylic compound (A) contains a compound having an isobornyl skeleton, it is preferred that the percentage of the compound having an isobornyl skeleton relative to the overall acrylic compound (A) is greater than 0 mass % and 80 mass % or less. By making the percentage greater than 0 mass %, it is particularly easy to miniaturize the size of the droplets. In addition, by making the percentage less than 80 mass %, it is easy to reduce the escaping gas. In particular, in order to reduce the escaping gas, the percentage of the compound having an isobornyl skeleton relative to the overall acrylic compound (A) is preferably less than 40 mass %, and more preferably less than 20 mass %.

[0100] The compound having an isobornyl skeleton may contain, for example, one or more compounds selected from the group consisting of isobornyl acrylate and isobornyl methacrylate.

[0101] The acrylic compound (A) preferably contains a component (a) containing at least one compound having a viscosity of 20 mPa·s or less at 25° C. In this case, the component (a) can reduce the viscosity of the composition (X1). The compound included in the component (a) may be a compound included in the multifunctional acrylic compound (A1) or a compound included in the monofunctional acrylic compound (A2).

[0102] The ratio of component (a) to the total amount of acrylic acid compounds (A) is preferably 50% by mass or more and 100% by mass or less. In this case, the viscosity of the composition (X1) can be particularly low, and it is particularly easy to apply the composition (X1) by inkjet method. The ratio of component (a) is more preferably 60% by mass or more, and more preferably 70% by mass or more. In addition, the ratio of component (a) is more preferably 95% by mass or less, and more preferably 90% by mass or less.

[0103] It is preferred that component (a) contains a compound having a glass transition temperature of 80°C or higher. That is, it is preferred that component (a) contains a compound having a viscosity of 20 mPa·s or less at 25°C and a glass transition temperature of 80°C or higher. In this case, component (a) can reduce the viscosity of the composition (X1) and increase the glass transition temperature of the cured product. It is more preferred that component (a) contains a compound having a glass transition temperature of 90°C or higher, and it is further preferred that it contains a compound having a glass transition temperature of 100°C or higher. The upper limit of the glass transition temperature of the compound included in component (a) is not limited, for example, it is 150°C or lower.

[0104] Component (a) may contain, for example, at least one compound selected from the group consisting of isobornyl acrylate, dicyclopentanyl acrylate, neopentyl glycol diacrylate, 1,6-hexanediol diacrylate, polyethylene glycol 200 dimethacrylate, and polyethylene glycol 200 diacrylate.

[0105] It is preferred that component (a) contains at least one compound selected from the group consisting of isobornyl acrylate, neopentyl glycol diacrylate, 1,6-hexanediol diacrylate, polyethylene glycol 200 dimethacrylate, and polyethylene glycol 200 diacrylate. These compounds can particularly reduce the maximum peak value of the composition (X1), and thus can contribute to achieving a maximum peak value of 350 mPa·s or less and a ratio of the maximum peak value to the viscosity at 25° C. of 20 or less for the composition (X1).

[0106] It is particularly preferred that component (a) contains isobornyl acrylate. Isobornyl acrylate can reduce the maximum peak value of the composition (X1), increase the glass transition temperature of the cured product, and reduce the shrinkage of the composition (X1) during curing.

[0107] The total amount of isobornyl acrylate, neopentyl glycol diacrylate, 1,6-hexanediol diacrylate, polyethylene glycol 200 dimethacrylate and polyethylene glycol 200 diacrylate relative to the total amount of acrylic acid compounds (A) is preferably 50% by mass or more and 95% by mass or less. In this case, the maximum peak value can be reduced, the glass transition temperature of the cured product can be increased, and the shrinkage of the composition (X1) during curing can be reduced. The total amount of these compounds is more preferably 60% by mass or more, and further preferably 70% by mass or less.

[0108] The acrylic compound (A) may contain a component (b), which contains a compound having at least one skeleton selected from a dicyclopentadiene skeleton, a dicyclopentyl skeleton, a dicyclopentenyl skeleton and a bisphenol skeleton. Component (b) can improve the adhesion between the cured product and inorganic compounds such as silicon nitride and silicon oxide. The compound included in component (b) may be a compound included in the multifunctional acrylic compound (A1) or a compound included in the monofunctional acrylic compound (A2). The compound included in component (b) may be a compound included in component (a).

[0109] However, in order to reduce the size of satellite droplets when the size of droplets of the composition (X) ejected by the inkjet method becomes small, that is, to reduce the size of the droplets without causing satellite droplets, it is preferred that the acrylic compound (A) does not contain a compound having a dicyclopentadiene skeleton.

[0110] The ratio of component (b) to the total amount of acrylic acid compounds (A) is preferably 5% by mass or more and 50% by mass or less. If the ratio of component (b) is 5% by mass or more, the adhesion of the cured product is further improved. In addition, if the ratio of component (b) is 50% by mass or less, the maximum peak of the composition (X1) can be reduced, and the viscosity of the composition (X1) can be further reduced and the composition (X1) can be easily formed by an inkjet method. The ratio of component (b) is further preferably 30% by mass or more, and further preferably 40% by mass or less. It should be noted that the acrylic acid compound (A) may not contain component (b), in which case the maximum peak of the composition (X1) can be particularly reduced.

[0111] The component (b) may contain, for example, at least one compound selected from the group consisting of tricyclodecane dimethanol diacrylate, bisphenol A polyethoxy diacrylate, and bisphenol F polyethoxy diacrylate.

[0112] It is also preferred that the acrylic compound (A) contains a component (c), wherein the component (c) is at least one component selected from the group consisting of a compound represented by the following formula (100), morpholine acrylate, diethyl acrylamide, dimethylaminopropyl acrylamide, and pentamethylpiperidinyl methacrylate. The component (c) can impart adhesion to a component made of an inorganic material such as a passivation layer 6 to the sealing material 5 made of the composition (X). The compound included in the component (c) may be a compound included in the component (a).

[0113] [Chemical formula 1]

[0114]

[0115] In formula (100), R 0 is H or methyl. X is a single bond or a divalent hydrocarbon group. 1 ~R 11 Each is H, alkyl or -R 12 -OH, R 12 is an alkylene group and R 1 ~R 11 At least one of them is alkyl or -R 12 -OH.R 1 ~R 11 There is no chemical bonding between them.

[0116] When X is a divalent hydrocarbon group, the number of carbon atoms of X is preferably 1 or more and 5 or less, more preferably 1 or more and 3 or less. The divalent hydrocarbon group is, for example, a methylene group, an ethylene group or a propylene group. X is particularly preferably a single bond or a methylene group. In this case, compound (A1) has the advantages of a small molecular weight and a low viscosity.

[0117] In R 1 ~R 11 In the case where at least one of the alkyl groups is an alkyl group, it is preferred that the number of carbon atoms of the alkyl group is greater than or equal to 1 and less than or equal to 8. The alkyl group is, for example, a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group or an octyl group. The alkyl group is linear and may have a branched chain. That is, for example, when the alkyl group is a butyl group, the butyl group may be a tert-butyl group, an n-butyl group or a sec-butyl group. When the alkyl group is a hexyl group, the hexyl group may be a tert-hexyl group, an n-butyl group or a sec-butyl group. When the alkyl group is an octyl group, the octyl group may be, for example, a tert-octyl group. It is particularly preferred that the alkyl group is a methyl group or a tert-butyl group. In this case, compound (A1) has the advantages of a small molecular weight and low viscosity.

[0118] In formula (100), it is preferred that an alkyl group or -R 12 -OH. That is, it is preferred that R 1 ~R 11 In, R6 and R 7 At least one of them is alkyl or -R 12 -OH, and the rest are each H. It is particularly preferred that R 1 ~R 11 In, only R 6 is alkyl or -R 12 -OH, and the rest are each H. In this case, the compound represented by formula (100) can have good reactivity and can easily provide the sealing material 5 with adhesion to the inorganic material component. This is considered to be because the cyclohexane ring in the compound represented by formula (100) has a boat-shaped stereo conformation, and the bulky alkyl group or -R at the 4-position 12 -OH is easily located in a pseudo-equatorial position. It is believed that by having such a structure in the compound represented by formula (100), the reactivity of the (meth)acryloyl group in the compound represented by formula (100) can be improved. In addition, if the compound represented by formula (100) has such a structure, the compound represented by formula (100) can increase the free volume in the sealing material 5. Therefore, it is believed that the interfacial free energy between the sealing material 5 and the parts made of inorganic materials is likely to be reduced, and thus the adhesion between the sealing material 5 and the parts made of inorganic materials is likely to be increased. Alkyl or -R 12 The larger the -OH volume, the larger the alkyl or -R 12 -OH is more likely to be in a pseudo-equatorial position. From this point of view, the alkyl group or -R 12 -OH is more preferred as it has more carbon atoms. In addition, alkyl or -R 12 -OH has a branched chain. For example, an alkyl group or -R 12 -OH is tert-butyl.

[0119] In formula (100), it is also preferred that an alkyl group or -R 12 -OH. That is, it is preferred that R 1 ~R 11 In, R 4 and R 5 At least one of them is alkyl or -R 12 -OH, R 8 and R 9 At least one of them is alkyl or -R 12 -OH, and the rest are each H. More preferably, R 1 ~R 11 In, only R 4 and R 5 One of them is alkyl or -R 12 -OH, R 8 and R 9 At least one of them is alkyl or -R 12-OH, and the rest are each H. Still more preferably, R 1 ~R 11 In, R 4 and R 5 At least one of them is alkyl or -R 12 -OH, R only 8 and R 9 One of them is alkyl or -R 12 -OH, and the rest are H. In this case, the compound represented by formula (100) can have good reactivity and can easily provide the sealing material 5 with adhesion to the inorganic material component. This is considered to be because the cyclohexane ring in the compound represented by formula (100) has a boat-shaped stereo conformation, and the 3- and 5-positions are each bulky alkyl or -R 12 -OH is easily located in a pseudo-equatorial position. Therefore, it is considered that the alkyl group or -R 12 In the case of -OH, the reactivity of the (meth)acryloyl group in the compound represented by formula (100) is improved, and the adhesion between the sealing material 5 and the inorganic material member is likely to be improved. 12 The larger the -OH volume, the larger the alkyl or -R 12 -OH is more likely to be in a pseudo-equatorial position. From this point of view, the alkyl group or -R 12 -OH is more preferred as it has more carbon atoms. In addition, alkyl or -R 12 -OH has a branched chain. For example, an alkyl group or -R 12 -OH is tert-butyl.

[0120] In R 1 ~R 11 At least one of them is -R 12 In the case of -OH, R 12 The number of carbon atoms in is preferably 1 or more and 5 or less, more preferably 1 or more and 3 or less. 12 For example, it is methylene, ethylene or propylene. 12 In this case, the compound (A1) has the advantages of small molecular weight and low viscosity.

[0121] In formula (100), R is particularly preferably 1 ~R 11 Each is H or alkyl, and R 1 ~R 11 At least one of the above is an alkyl group. In this case, the compound represented by formula (100) can have a particularly low viscosity, and therefore, the composition (X) can have a particularly low viscosity. Therefore, it is particularly easy to form the composition (X) by an inkjet method.

[0122] Preferably, component (c) comprises at least one compound selected from the group consisting of a compound represented by the following formula (110), a compound represented by the following formula (120), and a compound represented by the following formula (130). In this case, the shrinkage of the composition (X1) during curing can be particularly reduced. In addition, these compounds can also particularly improve the adhesion between the cured product and inorganic compounds such as silicon nitride and silicon oxide.

[0123] [Chemical formula 2]

[0124]

[0125] It is particularly preferred that the compound (A1) contains at least one of the compound represented by the formula (110) and the compound represented by the formula (120). In this case, it is particularly easy to reduce the viscosity of the composition (X), and it is particularly easy to increase the glass transition temperature of the sealing material 5, and it is particularly easy to increase the adhesion between the sealing material 5 and the parts made of inorganic materials. In addition, since the compound represented by the formula (110) and the compound represented by the formula (120) are not easy to volatilize, it is easy to improve the storage stability of the composition (X).

[0126] In addition, also preferably compound (A1) contains at least one component selected from morpholine acrylate, diethyl acrylamide, dimethylaminopropyl acrylamide and methacrylate pentamethyl piperidine ester. These compounds have good affinity with inorganic materials by comprising nitrogen, therefore, it is particularly easy to improve the closeness of the parts of sealing material 5 and inorganic material system. In addition, the viscosity of these compounds is low, therefore, these compounds are difficult for increasing the viscosity of composition (X). In addition, because these compounds are not volatile, it is easy to improve the storage stability of composition (X).

[0127] The amount of the compound (A1) is preferably 5% by mass or more and 80% by mass or less relative to the total amount of the acrylic compound (A). In this case, the sealing material 5 can have both a high glass transition temperature and adhesion to a component made of an inorganic material. The amount of the compound (A1) is more preferably 5% by mass or more and 60% by mass or less, and particularly preferably 5% by mass or more and 50% by mass or less.

[0128] When the composition (X1) contains a hygroscopic agent (C) described later, particularly when the hygroscopic agent (C) contains zeolite particles, it is preferred that the acrylic acid compound (A) does not contain a compound having nitrogen. Therefore, it is preferred that the acrylic acid compound (A) does not contain any of the above-mentioned morpholine acrylate, diethyl acrylamide, dimethylaminopropyl acrylamide and pentamethyl piperidinyl methacrylate. In this case, it is not easy to cause the viscosity of the composition (X1) to rise during the storage of the composition (X1). It is believed that this is because, if the composition (X1) contains a compound having nitrogen and a hygroscopic agent (C), the compound having nitrogen is easy to react with the hygroscopic agent (C).

[0129] The composition (X1) may further contain a radical polymerizable compound (E) other than the acrylic compound (A). The radical polymerizable compound (E) may contain either or both of a polyfunctional radical polymerizable compound (E1) having two or more radical polymerizable functional groups in one molecule and a monofunctional radical polymerizable compound (E2) having only one radical polymerizable functional group in one molecule. The amount of the radical polymerizable compound (E) is, for example, 10% by mass or less relative to the total amount of the acrylic compound (A) and the radical polymerizable compound (E). The polyfunctional radical polymerizable compound (E1) may, for example, contain at least one compound selected from aromatic carbamate oligomers, aliphatic carbamate oligomers, epoxy acrylate oligomers, polyester acrylate oligomers and other special oligomers having two or more ethylenic double bonds in one molecule. The monofunctional free radical polymerizable compound (E2) contains, for example, at least one compound selected from N-vinylformamide, vinyl caprolactam, vinyl pyrrolidone, phenyl glycidyl ether, p-tert-butylphenyl glycidyl ether, butyl glycidyl ether, 2-ethylhexyl glycidyl ether, allyl glycidyl ether, 1,2-butylene oxide, 1,3-butadiene oxide, 1,2-epoxydodecane, epichlorohydrin, 1,2-epoxydecane, styrene oxide, hexyl oxide, 3-vinyl hexyl oxide, 4-vinyl hexyl oxide, N-vinyl pyrrolidone and N-vinyl caprolactam.

[0130] The photoradical polymerization initiator (B) is not particularly limited as long as it is a compound that generates free radical species when irradiated with ultraviolet rays. The photoradical polymerization initiator (B) contains, for example, at least one compound selected from aromatic ketones, acylphosphine oxide compounds, aromatic onium salt compounds, organic peroxides, sulfur compounds (thioxanthone compounds, compounds containing thiophenyl, etc.), hexaarylbiimidazole compounds, ketoxime ester compounds, borate compounds, Azinium compounds (Azinium compounds), metallocene compounds, active ester compounds, compounds having carbon-halogen bonds, and alkylamine compounds. The amount of the photoradical polymerization initiator (B) relative to 100 parts by mass of the composition (X1) is, for example, 1 part by weight or more and 10 parts by weight or less.

[0131] The photoradical polymerization initiator (B) preferably contains a component having photobleaching properties. The component having photobleaching properties preferably contains an acylphosphine oxide-based photoinitiator, and preferably contains a compound having photobleaching properties among oxime ester-based photoinitiators.

[0132] It is also preferred that the photoradical polymerization initiator (B) contains a component having a sensitizer skeleton in the molecule. The sensitizer skeleton, for example, contains at least one of a 9H-thioxanthen-9-one skeleton and an anthracene skeleton. That is, it is preferred that the photoradical polymerization initiator (B) contains a component having at least one of a 9H-thioxanthen-9-one skeleton and an anthracene skeleton.

[0133] From the viewpoint of improving curability and preventing outgassing from the cured product, it is preferred that the photoradical polymerization initiator (B) contains an oxime ester-based photoinitiator regardless of whether the photoradical polymerization initiator (B) has photobleaching properties.

[0134] In order to reduce the risk of contamination of the composition (X) and the manufacturing apparatus due to the generation of decomposition products from the composition (X), and to reduce the risk of outgassing from the cured product, the oxime ester-based photoinitiator preferably comprises a compound having an aromatic ring, more preferably comprises a compound having a condensed ring containing an aromatic ring, and further preferably comprises a compound having a condensed ring containing a benzene ring and a heterocyclic ring.

[0135] The oxime ester photoinitiator may contain, for example, at least one compound selected from 1,2-octanedione-1-[4-(phenylthio)-, 2-(O-benzoyl oxime)] and ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(O-acetyl oxime) and oxime ester photoinitiators described in Japanese Patent Application Publication No. 2000-80068, Japanese Patent Application Publication No. 2001-233842, Japanese Patent Table No. 2010-527339, Japanese Patent Table No. 2010-527338, Japanese Patent Application Publication No. 2013-041153 and Japanese Patent Application Publication No. 2015-93842. The oxime ester photoinitiator may contain at least one compound selected from the commercially available Irgacure OXE-02 (manufactured by BASF), ADEKA ARKLS NCI-831, N-1919 (manufactured by ADEKA), and TR-PBG-304 (manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd.) having a carbazole skeleton, Irgacure OXE-01, ADEKA ARKLS NCI-930 (manufactured by ADEKA), TR-PBG-345, and TR-PBG-3057 (manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd.) having a diphenyl sulfide skeleton, and TR-PBG-365 (manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd.) and SPI-04 (manufactured by Samyang) having a fluorene skeleton. In particular, if the oxime ester photoinitiator contains a compound having a diphenyl sulfide skeleton or a fluorene skeleton, the cured product is less likely to be colored by photobleaching, which is preferred from this point of view. From the viewpoint of easily improving exposure sensitivity, it is preferred that the oxime ester-based photoinitiator contains a compound having a carbazole skeleton.

[0136] It is also preferred that the oxime ester photoinitiator contains two or more compounds. In this case, for example, by containing two or more compounds having different exposure sensitivities, the oxime ester photoinitiator can maintain good exposure sensitivity and reduce the amount of the photoradical polymerization initiator (B), thereby making it more difficult to generate outgassing from the cured product.

[0137] The composition (X1) may contain a polymerization accelerator in addition to the photoradical polymerization initiator (B). The polymerization accelerator may contain an amine compound such as ethyl p-dimethylaminobenzoate, 2-ethylhexyl p-dimethylaminobenzoate, methyl p-dimethylaminobenzoate, 2-dimethylaminoethyl benzoate, or butoxyethyl p-dimethylaminobenzoate.

[0138] The photoradical polymerization initiator (B) may contain a sensitizer as a part of the photoradical polymerization initiator (B). The sensitizer can promote the radical generation reaction of the photoradical polymerization initiator (B), improve the reactivity of the radical polymerization, and increase the crosslinking density. The sensitizer may contain, for example, at least one compound selected from 9,10-dibutoxyanthracene, 9-hydroxymethylanthracene, thioxanthone, 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2-chlorothioxanthone, 2,4-diethylthioxanthone, anthraquinone, 1,2-dihydroxyanthraquinone, 2-ethylanthraquinone, 1,4-diethoxynaphthalene, p-dimethylaminoacetophenone, p-diethylaminoacetophenone, p-dimethylaminobenzophenone, p-diethylaminobenzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, p-dimethylaminobenzaldehyde, and p-diethylaminobenzaldehyde.

[0139] The content of the sensitizer in the composition (X1) is, for example, 0.1 parts by mass or more and 5 parts by mass or less, preferably 0.1 parts by mass or more and 3 parts by mass or less, relative to 100 parts by mass of the solid content of the composition (X1). When the content of the sensitizer is within such a range, the composition (X1) can be cured in air, and there is no need to perform curing of the composition (X1) in an inert atmosphere such as a nitrogen atmosphere.

[0140] The composition (X1) may contain a polymerization accelerator in addition to the photoradical polymerization initiator (B). The polymerization accelerator may contain an amine compound such as ethyl p-dimethylaminobenzoate, 2-ethylhexyl p-dimethylaminobenzoate, methyl p-dimethylaminobenzoate, 2-dimethylaminoethyl benzoate, or butoxyethyl p-dimethylaminobenzoate.

[0141] When the curable component in the composition (X) contains the cationically polymerizable compound (F) and the cationic curing catalyst (G), the components of the composition (X) (hereinafter also referred to as the composition (X2)) will be described.

[0142] The cationically polymerizable compound (F) in the composition (X2) contains, for example, at least one of a polyfunctional cationically polymerizable compound (F1) and a monofunctional cationically polymerizable compound (F2).

[0143] The polyfunctional cationically polymerizable compound (F1) may contain either or both of a polyfunctional cationically polymerizable compound (F11) not having a siloxane skeleton and a polyfunctional cationically polymerizable compound (F12) having a siloxane skeleton.

[0144] The polyfunctional cationically polymerizable compound (F11) does not have a siloxane skeleton and has two or more cationically polymerizable functional groups per molecule. The number of cationically polymerizable functional groups per molecule of the polyfunctional cationically polymerizable compound (F11) is preferably 2 to 4, more preferably 2 to 3.

[0145] The cationically polymerizable functional group is, for example, at least one group selected from an epoxy group, an oxetanyl group, and a vinyl ether group.

[0146] The polyfunctional cationically polymerizable compound (F11) contains, for example, at least one compound selected from the group consisting of polyfunctional alicyclic epoxy compounds, polyfunctional heterocyclic epoxy compounds, polyfunctional oxetane compounds, alkylene glycol diglycidyl ethers, and alkylene glycol monovinyl monoglycidyl ethers.

[0147] The polyfunctional alicyclic epoxy compound contains, for example, either or both of a compound represented by the following formula (1) and a compound represented by the following formula (20).

[0148] [Chemical formula 3]

[0149]

[0150] In formula (1), R 1 ~R 18 Each is independently a hydrogen atom, a halogen atom, or a hydrocarbon group. The number of carbon atoms in the hydrocarbon group is preferably in the range of 1 to 20. Examples of the hydrocarbon group are alkyl groups having 1 to 20 carbon atoms such as methyl, ethyl, and propyl groups; alkenyl groups having 2 to 20 carbon atoms such as vinyl and allyl groups; or alkylidene groups having 2 to 20 carbon atoms such as ethylidene and propylidene groups. The hydrocarbon group may contain an oxygen atom or a halogen atom. R 1 ~R 18 Each independently is preferably a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms, more preferably a hydrogen atom or a methyl group, and most preferably a hydrogen atom.

[0151] In formula (1), X is a single bond or a divalent organic group, and an example of the organic group is -CO-O-CH2-.

[0152] Examples of the compound represented by the formula (1) include a compound represented by the following formula (1a) and a compound represented by the following formula (1b).

[0153] [Chemical formula 4]

[0154]

[0155] [Chemical formula 5]

[0156]

[0157] [Chemical formula 6]

[0158]

[0159] In formula (20), R 1 ~R 12 Each is independently a hydrogen atom, a halogen atom, or a hydrocarbon group having 1 to 20 carbon atoms. Examples of the halogen atom are fluorine, chlorine, bromine, or iodine. Examples of the hydrocarbon group having 1 to 20 carbon atoms are alkyl groups having 1 to 20 carbon atoms such as methyl, ethyl, and propyl; alkenyl groups having 2 to 20 carbon atoms such as vinyl and allyl; or alkylidene groups having 2 to 20 carbon atoms such as ethylidene and propylidene. The hydrocarbon group having 1 to 20 carbon atoms may contain an oxygen atom or a halogen atom.

[0160] R 1 ~R 12 Each independently is preferably a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms, more preferably a hydrogen atom or a methyl group, and most preferably a hydrogen atom.

[0161] Examples of the compound represented by the formula (20) include tetrahydroindene diepoxide represented by the following formula (20a).

[0162] [Chemical formula 7]

[0163]

[0164] The polyfunctional heterocyclic epoxy compound includes, for example, a trifunctional epoxy compound represented by the following formula (2).

[0165] [Chemical formula 8]

[0166]

[0167] The polyfunctional oxetane compound includes, for example, a bifunctional oxetane compound represented by the following formula (3).

[0168] [Chemical formula 9]

[0169]

[0170] The alkylene glycol diglycidyl ether contains, for example, at least one compound selected from the group consisting of compounds represented by the following formulae (4) to (7).

[0171] [Chemical formula 10]

[0172]

[0173] [Chemical formula 11]

[0174]

[0175] [Chemical formula 12]

[0176]

[0177] [Chemical formula 13]

[0178]

[0179] The alkylene glycol monovinyl monoglycidyl ether includes, for example, a compound represented by the following formula (8).

[0180] [Chemical formula 14]

[0181]

[0182] More specifically, the polyfunctional cationically polymerizable compound (F11) may contain, for example, at least one component selected from CELLOXIDE 2021P and CELLOXIDE 8010 manufactured by Daicel, TEPIC-VL manufactured by Nissan Chemical, OXT-221 manufactured by Toagosei, and 1,3-PD-DEP, 1,4-BG-DEP, 1,6-HD-DEP, NPG-DEP and butanediol monovinyl monoglycidyl ether manufactured by Yokkaichi Kogyo.

[0183] It is preferred that the polyfunctional cationically polymerizable compound (F11) contains a polyfunctional alicyclic epoxy compound. In this case, the composition (X2) can have particularly high cationic polymerization reactivity.

[0184] The polyfunctional alicyclic epoxy compound particularly preferably contains one or both of the compound represented by formula (1) and the compound represented by formula (20). In this case, the composition (X2) can have higher cationic polymerization reactivity.

[0185] When the polyfunctional alicyclic epoxy compound contains a compound represented by formula (1), it is preferred that the compound represented by formula (1) contains a compound represented by formula (1a). In this case, the composition (X2) can have higher cationic polymerization reactivity and particularly low viscosity.

[0186] In addition, in particular, the compound shown in formula (20) has low viscosity, so when containing the compound shown in formula (20), the composition (X2) can have good ultraviolet curability and can have particularly low viscosity. Furthermore, even if the compound shown in formula (20) has low viscosity, it also has a property of not being easily volatile. Therefore, even if the composition (X2) contains the compound shown in formula (20), the composition (X2) is not easy to change its composition due to the volatilization of the compound shown in formula (20). Therefore, the composition (X2) can be low-viscosity without damaging the storage stability by containing the compound shown in formula (20).

[0187] The compound represented by the formula (20) can be synthesized, for example, by oxidizing a cyclic olefin compound having a tetrahydroindene skeleton using an oxidizing agent.

[0188] The compound shown in formula (20) may include 4 stereoisomers based on the stereo configuration of 2 epoxy rings. The compound shown in formula (20) may include any one of the 4 stereoisomers. That is, the compound shown in formula (20) may contain at least one component selected from the 4 stereoisomers. The ratio of the total amount of the exo-endo-endo form and the endo-endo-endo form in the 4 stereoisomers in the compound shown in formula (20) is preferably 10% by mass or less, and more preferably 5% by mass or less relative to the epoxy compound (A1) as a whole. In this case, the heat resistance of the cured product can be improved. It should be noted that the ratio of a specific stereoisomer in the compound shown in formula (20) can be obtained based on the peak area ratio appearing in the chromatogram obtained by gas chromatography.

[0189] In order to reduce the amount of exo-endo and endo-endo in the compound represented by formula (20), an appropriate method such as a method of precision distilling the compound represented by formula (20) or a method of using column chromatography using silica gel as a filler can be used.

[0190] When the composition (X2) contains a polyfunctional cationic polymerizable compound (F11), the ratio of the polyfunctional cationic polymerizable compound (F11) to the total amount of the resin component is preferably in the range of 5 to 95% by mass. It should be noted that the resin component refers to a cationic polymerizable compound in the composition (X2), including a polyfunctional cationic polymerizable compound (F1) and a monofunctional cationic polymerizable compound (F2). If the ratio of the polyfunctional cationic polymerizable compound (F11) is 5% by mass or more, the composition (X2) can have particularly excellent reactivity during photocationic polymerization, and the cured product can have high strength (hardness). In addition, if the ratio of the polyfunctional cationic polymerizable compound (F11) is 95% by mass or less, when the composition (X2) contains a hygroscopic agent (C), the hygroscopic agent (C) can be easily dispersed particularly uniformly in the composition (X2). The proportion of the polyfunctional cationic polymerizable compound (F11) is more preferably 12% by mass or more, more preferably 15% by mass or more, more preferably 20% by mass or more, and particularly preferably 25% by mass or more. In addition, the proportion of the polyfunctional cationic polymerizable compound (F11) is more preferably 85% by mass or less, more preferably 60% by mass or less. For example, the proportion of the polyfunctional cationic polymerizable compound (F11) is preferably in the range of 20 to 60% by mass.

[0191] When the polyfunctional cationically polymerizable compound (F11) contains a polyfunctional alicyclic epoxy compound, the polyfunctional alicyclic epoxy compound may be a part of the polyfunctional cationically polymerizable compound (F11) or the whole of the polyfunctional cationically polymerizable compound (F11). The ratio of the polyfunctional alicyclic epoxy compound to the polyfunctional cationically polymerizable compound (F11) is preferably in the range of 15 to 100% by mass. If the ratio is 15% by mass or more, the polyfunctional alicyclic epoxy compound can particularly contribute to improving the ultraviolet curability of the composition (X2).

[0192] The multifunctional cationic polymerizable compound (F12) has a siloxane skeleton and two or more cationic polymerizable functional groups per molecule. The number of cationic polymerizable functional groups per molecule of the multifunctional cationic polymerizable compound (F12) is preferably 2 to 6, and more preferably 2 to 4. The multifunctional cationic polymerizable compound (F12) can help improve the cationic polymerization reactivity of the composition (X2), and can help improve the heat discoloration resistance of the cured product and the sealing material 5. If the heat discoloration resistance of the sealing material 5 is high, the time-dependent degradation of the luminous intensity and the time-dependent change of the luminous color of the light-emitting device 1 equipped with the sealing material 5 can be suppressed. In addition, the multifunctional cationic polymerizable compound (F12) can also contribute to the low elastic modulus of the cured product and the sealing material 5, and therefore, flexibility can also be imparted to the light-emitting device 1 equipped with the sealing material 5. In addition, when the composition (X2) contains a hygroscopic agent, the multifunctional cationic polymerizable compound (F12) can help improve the dispersibility of the hygroscopic agent in the composition (X2) and the cured product. Therefore, even when the moisture absorbent is not subjected to surface treatment for improving dispersibility, the moisture absorbent can be well dispersed in the composition (X2) and the cured product.

[0193] The polyfunctional cationically polymerizable compound (F12) is preferably liquid at 25° C. The viscosity of the polyfunctional cationically polymerizable compound (F12) at 25° C. is particularly preferably in the range of 10 to 300 mPa·s. In this case, an increase in the viscosity of the composition (X2) can be suppressed.

[0194] The cationically polymerizable functional group possessed by the polyfunctional cationically polymerizable compound (F12) is, for example, at least one group selected from the group consisting of an epoxy group, an oxetanyl group, and a vinyl ether group.

[0195] The siloxane skeleton possessed by the multifunctional cationic polymerizable compound (F12) may be linear, branched or cyclic. The number of Si atoms possessed by the siloxane skeleton is preferably in the range of 2 to 14. In this case, the composition (X2) may have a particularly low viscosity. The number of Si atoms is more preferably in the range of 2 to 10, further preferably in the range of 2 to 7, and particularly preferably in the range of 3 to 6.

[0196] The polyfunctional cationically polymerizable compound (F12) contains, for example, at least one of a compound represented by the formula (10) and a compound represented by the formula (11).

[0197] [Chemical formula 15]

[0198]

[0199] [Chemical formula 16]

[0200]

[0201] R in each of formula (10) and formula (11) is a single bond or a divalent organic group, preferably an alkylene group. Y is a siloxane skeleton, which may be any of a linear, branched, and cyclic structure, and the number of Si atoms is preferably in the range of 2 to 14, more preferably in the range of 2 to 10, further preferably in the range of 2 to 7, and particularly preferably in the range of 3 to 6. n is an integer greater than 2, preferably in the range of 2 to 4.

[0202] More specifically, for example, the polyfunctional cationically polymerizable compound (F12) contains a compound represented by the following formula (10a).

[0203] [Chemical formula 17]

[0204]

[0205] R in formula (10a) is a single bond or a divalent organic group, and is preferably an alkylene group having 1 to 4 carbon atoms. n in formula (10a) is an integer greater than 0. n is preferably in the range of 0 to 12, more preferably in the range of 0 to 8, further preferably in the range of 0 to 5, and particularly preferably in the range of 1 to 4.

[0206] The compound represented by the formula (10a) preferably contains a compound represented by the following formula (30). That is, the polyfunctional cationically polymerizable compound (F12) preferably contains a compound represented by the following formula (30).

[0207] [Chemical formula 18]

[0208]

[0209] In formula (30), n is an integer greater than or equal to 0, preferably in the range of 0-12, more preferably in the range of 0-8, further preferably in the range of 0-5, and particularly preferably in the range of 1-4.

[0210] Examples of the compound represented by the formula (30) include a compound represented by the following formula (10a-1).

[0211] [Chemical formula 19]

[0212]

[0213] The multifunctional cationic polymerizable compound (F12) may contain at least one of the compounds represented by the following formulae (10b) to (10d) and (11a) to (11b) instead of the compound represented by formula (10a), or may contain at least one of the compounds represented by the following formulae (10b) to (10d) and (11a) to (11b) together with the compound represented by formula (10a).

[0214] [Chemical formula 20]

[0215]

[0216] [Chemical formula 21]

[0217]

[0218] [Chemical formula 22]

[0219]

[0220] R in formula (10d) is a single bond or a divalent organic group, and is preferably an alkylene group having 1 to 4 carbon atoms. n in formula (10d) is an integer of 0 or more. m in formula (10d) is an integer of 2 or more.

[0221] [Chemical formula 23]

[0222]

[0223] R in formula (11a) is a single bond or a divalent organic group, preferably an alkylene group having 1 to 4 carbon atoms. n in formula (11a) is an integer greater than 0, preferably in the range of 8 to 80. m in formula (11a) is an integer greater than 2, preferably in the range of 2 to 6.

[0224] [Chemical formula 24]

[0225]

[0226] R in formula (11b) is a single bond or a divalent organic group, and is preferably an alkylene group having 1 to 4 carbon atoms. n in formula (11b) is an integer greater than or equal to 0, and is preferably in the range of 8 to 80.

[0227] More specifically, it is preferred that the polyfunctional cationic polymerizable compound (F12) contains, for example, at least one component selected from product numbers X-40-2669, X-40-2670, X-40-2715, X-40-2732, X-22-169AS, X-22-169B, X-22-2046, X-22-343, X-22-163 and X-22-163B manufactured by Shin-Etsu Chemical Co., Ltd.

[0228] It is preferred that the polyfunctional cationic polymerizable compound (F12) has an alicyclic epoxy structure, and it is particularly preferred that the polyfunctional cationic polymerizable compound (F12) contains a compound represented by formula (10a). The compound represented by formula (10a) can be particularly helpful in improving the cationic polymerization reactivity and low viscosity of the composition (X2), and can be particularly helpful in improving the heat discoloration resistance and low elastic modulus of the cured product and the sealing material 5. When the composition (X2) contains a hygroscopic agent (C), it can also be particularly helpful in improving the dispersibility of the hygroscopic agent (C) in the composition (X2).

[0229] When the composition (X2) contains a polyfunctional cationic polymerizable compound (F12), the ratio of the polyfunctional cationic polymerizable compound (F12) to the total amount of the resin component is preferably in the range of 5 to 95% by mass. If the ratio of the polyfunctional cationic polymerizable compound (F12) is 5% by mass or more, especially when the composition (X2) contains a hygroscopic agent (C), the dispersibility of the hygroscopic agent (C) in the composition (X2) and in the cured product is particularly improved, thereby improving the transparency of the cured product. In addition, if the ratio of the polyfunctional cationic polymerizable compound (F12) is 95% by mass or less, the composition (X2) can have a particularly high photocationic polymerization reactivity, and therefore, the cured product can have a particularly high strength (hardness). The ratio of the polyfunctional cationic polymerizable compound (F12) is more preferably 6% by mass or more, further preferably 13% by mass or more, and particularly preferably 20% by mass or more. In addition, the ratio of the polyfunctional cationic polymerizable compound (F12) is more preferably 70% by mass or less, in which case, the cured product can have a high refractive index. The ratio of the polyfunctional cationically polymerizable compound (F12) is more preferably 45% by mass or less. For example, the ratio of the polyfunctional cationically polymerizable compound (F12) is preferably in the range of 20 to 70% by mass.

[0230] The monofunctional cationically polymerizable compound (F2) has only one cationically polymerizable functional group per molecule. The cationically polymerizable functional group is, for example, at least one group selected from the group consisting of an epoxy group, an oxetanyl group, and a vinyl ether group.

[0231] The viscosity of the monofunctional cationically polymerizable compound (F2) at 25°C is preferably 8 mPa·s or less. In this case, even if the composition (X2) does not contain a solvent, the monofunctional cationically polymerizable compound (F2) can reduce the viscosity of the composition (X2). It is particularly preferred that the viscosity of the monofunctional cationically polymerizable compound (F2) at 25°C is in the range of 0.1 to 8 mPa·s.

[0232] The monofunctional cationically polymerizable compound (F2) may contain, for example, at least one compound selected from the group consisting of compounds represented by the following formulae (12) to (17) and limonene oxide.

[0233] [Chemical formula 25]

[0234]

[0235] [Chemical formula 26]

[0236]

[0237] [Chemical formula 27]

[0238]

[0239] [Chemical formula 28]

[0240]

[0241] [Chemical formula 29]

[0242]

[0243] [Chemical formula 30]

[0244]

[0245] The monofunctional cationic polymerizable compound (F2) particularly preferably contains a compound represented by the above formula (16). In this case, the viscosity of the composition (X2) can be reduced. In addition, among the components that the monofunctional cationic polymerizable compound (F2) can contain, the compound represented by the formula (16) has a high boiling point and low volatility, so the viscosity of the composition (X2) can be effectively suppressed over time. Therefore, the composition (X2) can have good coating properties even when stored for a long time, and can also maintain good inkjet coating properties.

[0246] The ratio of the monofunctional cationically polymerizable compound (F2) to the total amount of the resin component is preferably in the range of 5 to 50% by mass. If the ratio of the monofunctional cationically polymerizable compound (F2) is 5% by mass or more, the viscosity of the composition (X2) can be particularly reduced. In addition, if the ratio of the monofunctional cationically polymerizable compound (F2) is 50% by mass or less, the composition (X2) can have particularly excellent reactivity during the photocationic polymerization reaction, and thereby the cured product can have high strength (hardness). The ratio of the monofunctional cationically polymerizable compound (F2) is more preferably 10% by mass or more, and further preferably 15% by mass or more. In addition, the ratio of the monofunctional cationically polymerizable compound (F2) is more preferably 40% by mass or less, further preferably 35% by mass or less, and particularly preferably 30% by mass or less. In particular, if the proportion of the monofunctional cationic polymerizable compound (F2) is 35% by mass or less, the volatilization amount of the components in the composition (X2) during the storage of the composition (X2) can be effectively reduced, so that even if the composition (X2) is stored for a long time, the characteristics of the composition (X2) are not easily impaired. In addition, the viscosity of the cured product can be particularly suppressed. For example, the proportion of the monofunctional cationic polymerizable compound (F2) is preferably in the range of 10 to 35% by mass.

[0247] In addition, in particular, when the composition (X2) contains a polyfunctional cationically polymerizable compound (F11) and a polyfunctional cationically polymerizable compound (F12), the proportion of the polyfunctional cationically polymerizable compound (F11) is preferably in the range of 30 to 60% by mass, the proportion of the polyfunctional cationically polymerizable compound (F12) is in the range of 15 to 30% by mass, and the proportion of the monofunctional cationically polymerizable compound (F2) is in the range of 15 to 40% by mass relative to the total amount of the resin component. In this case, the good storage stability, low viscosity and good cationic polymerization reactivity of the composition (X2) can be achieved in a balanced manner, and the excellent transparency, excellent hygroscopicity and high refractive index of the cured product can be achieved in a balanced manner.

[0248] Preferably, the composition (X2) contains a sensitizer (H). In this case, the composition (X2) can have particularly high cationic polymerization reactivity. The sensitizer (H) contains, for example, either or both of 9,10-dibutoxyanthracene and 9,10-diethoxyanthracene. The ratio of the sensitizer (H) to the total amount of the resin component is preferably in the range of greater than 0% by mass and less than 1% by mass. In this case, the sensitizer (H) is not likely to hinder the transparency of the cured product, so the cured product can have good transparency.

[0249] The cationic curing catalyst (G) is not particularly limited as long as it generates a protonic acid or a Lewis acid when irradiated with light. The cationic curing catalyst (G) may contain at least one of an ionic photoacid generating cationic curing catalyst and a nonionic photoacid generating cationic curing catalyst.

[0250] The ionic photoacid generating type cationic curing catalyst may contain at least one of an onium salt and an organic metal complex. Examples of onium salts include aromatic diazonium salts, aromatic onium salts, and aromatic sulfonium salts. Examples of organic metal complexes include iron-arene complexes, titanocene complexes, and arylsilanol-aluminum complexes. The ionic photoacid generating type cationic curing catalyst may contain at least one of these components.

[0251] The cationic curing catalyst of the nonionic photoacid generator may contain, for example, at least one component selected from nitrobenzyl esters, sulfonic acid derivatives, phosphoric acid esters, phenolsulfonic acid esters, naphthoquinone diazide, and N-hydroxyimidophosphonic acid esters.

[0252] More specific examples of the compound that can be contained in the cationic curing catalyst (G) include DPI series (105, 106, 109, 201, etc.), BI-105, MPI series (103, 105, 106, 109, etc.), BBI series (101, 102, 103, 105, 106, 109, 110, 200, 210, 300, 301, etc.), TSP series manufactured by MIDORI Chemical (102, 103, 105, 106, 109, 200, 300, 1000, etc.), HDS-109, MDS series (103, 105, 109, 203, 205, 209, etc.), BDS-109, MNPS-109, DTS series (102, 103, 105, 200, etc.), NDS series (103, 105, 155, 165, etc.), DAM series (101, 102, 103, 105, 201, etc.), SI series (105, 106, etc.), PI-106, NDI series (105, 106, 109, 1001, 1004, etc.), PAI series (01, 101, 106, 1001, 1002, 1003, 1004, etc.), MBZ-101, PYR-100, NB series (101, 201, etc.), NAI series (100, 1002, 1003, 1004, 101, 105, 106, 109, etc.), TAZ series (100, 101, 102, 103, 104, 107, 108, 109, 110, 113, 114, 118, 122, 123, 203, 204, etc.), NBC-101, ANC-101, TPS-Acetate, DTS-Acetate, Di-Boc Bisphinol A, tert-Butyl lithocholate, tert-Butyl deoxycholate, tert-Butylcholate, BX, BC-2, MPI-103, BDS-105, TPS-103, NAT-103, BMS-105 and TMS-105;

[0253] Cyracure UVI-6970, Cyracure UVI-6974, Cyracure UVI-6990 and Cyracure UVI-950 manufactured by Union Carbide, USA;

[0254] Irgacure 250, Irgacure 261 and Irgacure 264 manufactured by BASF;

[0255] CG-24-61 manufactured by CIBA-GEIGY;

[0256] Adeka Optomer SP-150, Adeka Optomer SP-151, Adeka Optomer SP-170 and Adeka Optomer SP-171 manufactured by ADEKA Co., Ltd.;

[0257] DAICAT II manufactured by Daicel Co., Ltd.;

[0258] UVAC1590 and UVAC1591 manufactured by Daicel-Cytec Co., Ltd.;

[0259] CI-2064, CI-2639, CI-2624, CI-2481, CI-2734, CI-2855, CI-2823, CI-2758 and CIT-1682 manufactured by Nippon Soda Co., Ltd.;

[0260] Tetrakis(pentafluorophenyl)borate toluoylcumyl iodonium salt PI-2074 manufactured by RHODIA;

[0261] FFC509 made by 3M;

[0262] CD-1010, CD-1011 and CD-1012 made by Sartomer of the United States;

[0263] CPI-100P, CPI-101A, CPI-110P, CPI-110A and CPI-210S manufactured by San-apro Co., Ltd.; and

[0264] UVI-6992 and UVI-6976 manufactured by The Dow Chemical Company. The cationic curing catalyst (G) may contain at least one compound selected from these compounds.

[0265] The ratio of the cationic curing catalyst (G) to the total amount of the resin component is preferably in the range of 1 to 4% by mass. By making the ratio 1% by mass or more, the composition (X2) can have particularly good cationic polymerization reactivity. In addition, by making the ratio 4% by mass or less, the composition (X2) can have good storage stability, and in addition, by not containing excessive cationic curing catalyst (G), the manufacturing cost can be reduced.

[0266] No matter what kind of curable component composition (X) contains, composition (X) can further contain hygroscopic agent (C). That is, composition (X1) can further contain hygroscopic agent (C), and composition (X2) can also further contain hygroscopic agent (C). If composition (X) contains hygroscopic agent (C), the cured product can have excellent hygroscopicity. The average particle diameter of hygroscopic agent (C) is preferably less than 200nm. In this case, despite containing hygroscopic agent (C), the cured product can also have high transparency. In addition, particularly in the case of applying composition (X) by inkjet method, if the average particle diameter of hygroscopic agent (C) is less than 200nm, there is the advantage that composition (X) is not easy to clog nozzle. In addition, if the average particle diameter of hygroscopic agent (C) is less than 200nm, hygroscopic agent (C) is not easy to damage the smoothness of the surface of the sealing material made by composition (X). Therefore, the surface of the sealing material can have good smoothness.

[0267] As described above, by the hygroscopic agent (C), the cured product can have high hygroscopicity. The moisture absorption rate of the cured product is preferably 0.5% by mass or more, more preferably 1% by mass or more, and most preferably 2% by mass or more. It should be noted that the moisture absorption rate is obtained by the following method. After applying the composition (X) under an argon atmosphere, ultraviolet rays are irradiated to prepare a film with a thickness of 10 μm. The ultraviolet irradiation conditions are, for example, a peak wavelength of ultraviolet rays of 365 nm and an ultraviolet intensity of 3000 mW / cm 2 , the ultraviolet irradiation time is 10 seconds. For example, use a vacuum dryer to vacuum dry the film under the conditions of a heating temperature of 120°C and a heating time of 3 hours. Measure the mass of the dried film. The measurement result is referred to as the initial mass (M0). Next, allow the film to fully absorb moisture. To this end, for example, the film is exposed to the conditions of 85°C and 85% RH for 24 hours. Measure the mass of the film after moisture absorption. The measurement result is referred to as the mass after moisture absorption (M). Based on these initial mass (M0) and mass after moisture absorption (M), the moisture absorption rate can be calculated using the formula (M-M0) / M0×100 (mass %).

[0268] The moisture absorbent (C) is preferably an inorganic particle having moisture absorbency, and preferably contains at least one component selected from zeolite particles, silica gel particles, calcium chloride particles, and titanium oxide nanotube particles. In particular, the moisture absorbent (C) preferably contains zeolite particles.

[0269] Zeolite particles with an average particle size of less than 200 nm can be manufactured, for example, by crushing conventional industrial zeolites. When manufacturing zeolite particles, the zeolite can be crystallized by hydrothermal synthesis after crushing the zeolite. In this case, the zeolite particles can have particularly high hygroscopicity. The manufacturing method of such zeolite particles is disclosed in Japanese Patent Publication No. 2016-69266, Japanese Patent Publication No. 2013-049602, etc.

[0270] The zeolite particles are preferably made from a zeolite containing sodium ions as a raw material, and among the zeolites containing sodium ions, at least one selected from type A zeolite, type X zeolite, and type Y zeolite is more preferably used as a raw material. It is particularly preferred to use type 4A zeolite among type A zeolites as a raw material to make the zeolite particles. In these cases, the zeolite particles have a crystal structure suitable for adsorbing water.

[0271] A specific example of a method for producing zeolite particles having an average particle size of 200 nm or less is shown. First, zeolite powder as a raw material is prepared, and the zeolite powder is physically crushed. For example, zeolite powder is mixed with water to prepare a slurry, and the slurry is placed in a bead mill, thereby physically crushing the zeolite powder.

[0272] Next, the zeolite powder is crystallized by hydrothermal synthesis. For example, the hydrothermal synthesis can be performed by heating a slurry containing physically crushed zeolite powder in an autoclave. The conditions of the hydrothermal synthesis are, for example, a heating temperature in the range of 150 to 200° C. and a heating time in the range of 15 to 24 hours.

[0273] Next, the zeolite powder is dried. The drying temperature is, for example, in the range of 150 to 200° C., and the drying time is, for example, in the range of 2 to 3 hours. Next, if necessary, the dried zeolite powder is crushed using a mortar or the like and then sieved to adjust the particle size.

[0274] Next, the zeolite powder is subjected to an ion exchange treatment as necessary. In particular, when the zeolite powder is a sodium-containing zeolite such as LTA, it is preferable to perform an ion exchange treatment to exchange the sodium in the zeolite powder with magnesium.

[0275] The ion exchange treatment is carried out, for example, by dispersing zeolite powder in an aqueous solution containing magnesium ions to prepare a mixture, and heating the mixture. More specifically, the ion exchange treatment is carried out, for example, as follows. First, zeolite powder is mixed with magnesium chloride and water, and the resulting mixture is heated while being stirred. During the treatment, it is preferred to repeat the operation of temporarily stopping stirring several times at appropriate intervals, discarding the supernatant of the mixture, and then adding water to the mixture and starting stirring again. The heating temperature in the treatment is preferably in the range of 40 to 80°C, and the treatment time is in the range of 6 to 8 hours.

[0276] When the ion exchange treatment is performed, the zeolite powder is then dried. The drying temperature is, for example, in the range of 150 to 200° C., and the drying time is, for example, in the range of 2 to 3 hours. Next, the dried zeolite powder is crushed using a mortar or the like and sieved as needed to adjust the particle size. Thus, zeolite particles with an average particle size of 200 nm or less can be obtained.

[0277] The crystallization of zeolite powder can also be carried out in the presence of silicates and alkali metal oxides. A specific example of a method for producing zeolite particles having an average particle size of 200 nm or less in this case is shown. First, zeolite powder is prepared. The zeolite powder preferably has a composition of aM12O·bSiO2·Al2O3·cMe. M1 is an alkali metal, a proton or an ammonium ion (NH4 + ), Me is an alkaline earth metal, a is a number in the range of 0.01 to 1, b is a number in the range of 20 to 80, and c is a number in the range of 0 to 1. The zeolite powder preferably contains a zeolite containing sodium ions, and among the zeolites containing sodium ions, it is more preferred to contain at least one material selected from type A zeolite, type X zeolite and type Y zeolite. The zeolite powder particularly preferably contains type 4A zeolite among type A zeolite. The zeolite powder is physically crushed. For example, the zeolite powder can be physically crushed by placing it in a bead mill.

[0278] The physically crushed zeolite powder is dispersed in a solution containing M22O, SiO2 and H2O to prepare a slurry. M2 is an alkali metal, preferably K or Na. The molar ratio of M22O / H2O is, for example, in the range of 0.003 to 0.01, and the molar ratio of SiO2 / H2O is, for example, in the range of 0.006 to 0.025. The amount of zeolite powder is, for example, 0.5 to 10 g relative to 100 ml of the solution.

[0279] The zeolite powder can be crystallized by heating the slurry in an autoclave. The conditions are, for example, a heating temperature in the range of 100 to 230° C. and a heating time in the range of 1 to 24 hours. Next, the zeolite powder is washed and dried. Thus, zeolite particles with an average particle size of 200 nm or less can be obtained.

[0280] The pH of the zeolite particles is preferably above 7 and below 10. If the pH of the zeolite particles is above 7, the crystals of the zeolite particles are not easily destroyed, and therefore, the sealing material made from the composition (X) containing the zeolite particles can have particularly high hygroscopicity. In addition, if the pH of the zeolite particles is below 10, when the composition (X) is cured, the zeolite particles are not likely to hinder the curing.

[0281] The pH of the zeolite particles is a value obtained by adding 0.05 g of zeolite particles to 99.95 g of ion-exchanged water to obtain a dispersion, heating the dispersion at 90° C. for 24 hours, and then measuring the pH of the supernatant of the dispersion using a pH meter. As the pH meter, for example, a small pH meter <LAQUAtwin> B-711 manufactured by Horiba, Ltd. can be used.

[0282] In order to adjust the pH of the zeolite particles to 7 or more and 10 or less, the zeolite particles are preferably composed of FAU Y-type zeolite having protons as counter cations.

[0283] In the process of producing zeolite particles, when performing hydrothermal synthesis of zeolite, a treatment for adjusting pH may be performed. The treatment for adjusting pH is performed, for example, before heating the slurry containing zeolite powder prepared for hydrothermal synthesis, during heating of the slurry, or after heating of the slurry. The pH is adjusted, for example, by adding an acid to the slurry. The acid contains, for example, at least one component selected from inorganic acids such as hydrochloric acid, sulfuric acid, and nitric acid, and organic acids such as formic acid, acetic acid, and oxalic acid.

[0284] The average particle size of the hygroscopic agent (C) is preferably more than 10nm and less than 200nm. If the average particle size is less than 200nm, the cured product can have particularly high transparency. In addition, if the average particle size is more than 10nm, the good hygroscopicity of the hygroscopic agent (C) can be maintained. It should be noted that the average particle size is the median particle size calculated from the measurement results obtained by the dynamic light scattering method, i.e., the cumulative 50% particle size (D50). It should be noted that as a measuring device, the Nanotrac Wave series of Microtrac BEL Co., Ltd. can be used.

[0285] The average particle size of the hygroscopic agent (C) is more preferably less than 150 nm, further preferably less than 100 nm, and particularly preferably less than 70 nm. In addition, the average particle size of the hygroscopic agent (C) is preferably more than 20 nm, more preferably more than 50 nm. In this case, the cured product can have particularly good transparency and hygroscopicity.

[0286] The cumulative 90% particle size (D90) of the moisture absorbent (C) is also preferably 100 nm or less. In this case, the cured product can have particularly high transparency.

[0287] The ratio of the total amount of hygroscopic agent (C) relative to the composition (X) is preferably 1% by mass or more and 20% by mass or less. If the ratio of hygroscopic agent (C) is 1% by mass or more, the cured product can have particularly high hygroscopicity. In addition, if the ratio of hygroscopic agent (C) is 20% by mass or less, the viscosity of the composition (X) can be particularly reduced, and the composition (X) can have a sufficiently low viscosity to the extent that it can be applied by inkjet. The ratio of hygroscopic agent (C) is further preferably 3% by mass or more, particularly preferably 5% by mass or more. In addition, the ratio of hygroscopic agent (C) is more preferably 15% by mass or less, particularly preferably 13% by mass or less.

[0288] The composition (X) may further contain an inorganic filler other than the hygroscopic agent (C). In particular, it is preferred that the composition (X) contains nano-sized high refractive index particles. Examples of high refractive index particles include zirconium oxide particles. If the composition (X) contains high refractive index particles, it is possible to increase the refractive index of the cured product while maintaining good transparency of the cured product. Therefore, when the cured product is applied to the sealing material 5 in the light-emitting device 1, the extraction efficiency of light emitted to the outside through the sealing material 5 can be improved. The average particle size of the high refractive index particles is preferably in the range of 5 to 30 nm, and more preferably in the range of 10 to 20 nm.

[0289] The proportion of high refractive index particles in the composition (X) is appropriately designed so that the cured product has a desired refractive index. It is particularly preferred that high refractive index particles are contained in the composition (X) so that the refractive index of the cured product is within a range of 1.45 or more and less than 1.55. In this case, the light extraction efficiency of the light emitting device 1 is particularly high.

[0290] In the case where the composition (X) contains a hygroscopic agent (C), the composition (X) may further contain a dispersant (D). The dispersant (D) is a surfactant that can be adsorbed on the hygroscopic agent (C). The dispersant (D) has, for example, an adsorption group (also called an anchor) that can be adsorbed on the particles of the hygroscopic agent (C) and a chain-like or comb-like molecular skeleton, i.e., a tail, that is attached to the particles of the hygroscopic agent (C) by adsorption of the adsorption group. The dispersant (D) contains, for example, at least one component selected from the following dispersants: an acrylic dispersant whose tail is an acrylic molecular chain, a carbamate dispersant whose tail is a carbamate molecular chain, and a polyester dispersant whose tail is a polyester molecular chain.

[0291] If the composition (X) contains a dispersant (D), the hygroscopic agent (C) can be well dispersed in the composition (X) and in the cured product. Therefore, although the cured product and the sealing material 5 contain a hygroscopic agent (C), the transparency of the cured product and the sealing material 5 is not easily reduced by the hygroscopic agent (C). In addition, the dispersant (D) can effectively suppress the coagulation of the hygroscopic agent (C) during the storage of the composition (X). Therefore, the storage stability of the composition (X) is not easily reduced by the hygroscopic agent (C).

[0292] In addition, the adhesion between the cured product and silicon nitride and silicon oxide is not easily reduced by the dispersant (D). It is believed that this is because the dispersant (D) is easily adsorbed on the hygroscopic agent (C) as described above, so the dispersant (D) is not easy to affect the interface between the cured product and silicon nitride and silicon oxide. Therefore, the sealing material 5 can have a high adhesion with the glass substrate. In addition, silicon nitride and silicon oxide are sometimes used as materials for the passivation layer 6 in the light-emitting device 1. Therefore, in the case where the passivation layer 6 is made of silicon nitride or silicon oxide, the sealing material 5 can have a high adhesion with the passivation layer 6.

[0293] The boiling point of the dispersant (D) is preferably 200° C. or higher. In this case, the dispersant (D) is less likely to volatilize from the composition (X), so the storage stability of the composition (X) is further improved.

[0294] The dispersant (D) preferably has either or both of a basic polar functional group and an acidic polar functional group as an adsorption group. In this case, the hygroscopic agent (C) can be particularly well dispersed in the composition (X) and the cured product. This is believed to be because the dispersant (D) has either or both of a basic polar functional group and an acidic polar functional group, and is easily adsorbed on the hygroscopic agent (C), thereby significantly showing the effect of dispersing the hygroscopic agent (C).

[0295] The dispersant (D) may include a polymer. The weight average molecular weight of the polymer is, for example, 1000 or more. The polymer, for example, contains at least one component selected from hydroxyl-containing carboxylic acid esters, salts of long-chain polyaminoamide and high molecular weight acid esters, salts of high molecular weight polycarboxylic acids, salts of long-chain polyaminoamide and polar acid esters, high molecular weight unsaturated acid esters, modified polyurethanes, modified polyacrylates, polyether ester anionic active agents, salts of naphthalenesulfonic acid formaldehyde condensates, polyoxyethylene alkyl phosphates, polyoxyethylene nonylphenyl ethers, polyester polyamines, and stearylamine acetate. If the dispersant (D) contains a polymer, the steric hindrance effect generated when the polymer is adsorbed on the particles of the hygroscopic agent (C) is increased, thereby improving the dispersibility of the hygroscopic agent (C).

[0296] The dispersant (D) may contain, for example, either or both of a dispersant (F1) having a basic polar functional group and a dispersant (F2) having an acidic polar functional group.

[0297] The basic polar functional group in the dispersant (F1) having a basic polar functional group includes, for example, at least one group selected from an amino group, an imino group, an amide group, an imide group, and a nitrogen-containing heterocyclic group. If the dispersant (F1) has a basic polar functional group, the dispersant (F1) is easily adsorbed to the hygroscopic agent (C), thereby improving the dispersibility of the hygroscopic agent (C). The basic polar functional group preferably includes an amino group, because the amino group can particularly improve the adsorption capacity of the dispersant (F1) for the hygroscopic agent (C), can particularly improve the dispersibility of the hygroscopic agent (C), and can particularly reduce the viscosity of the composition (X).

[0298] The dispersant (F1) having a basic polar functional group includes, for example, Solsperse 24000 (amine value: 41.6 mgKOH / g), Solsperse 32000 (amine value: 31.2 mgKOH / g), Solsperse 39000 (amine value: 25.7 mgKOH / g), Solsperse J100, Solsperse J200 and other Solsperse series manufactured by Japan Lubrizol Co., Ltd.; trade names: DISPERBYK-108, DISPERBYK-2013, DISPERBYK-180, DISPERBYK-106, DISPERBYK-162 (amine value: 13mgKOH / g), trade name: DISPERB YK-163 (amine value: 10mgKOH / g), trade name: DISPERBYK-168 (amine value: 11mgKOH / g), trade name: DISPERBYK-2050 (amine value: 30.7mgKOH / g), trade name: DISPERBYK-2150 (amine value: 56.7mgKOH / g), etc. BYK-Chemie Japan Co., Ltd. DISPERBYK series; BYKJET series manufactured by BYK-Chemie Japan Co., Ltd., such as product name: BYKJET-9151 (amine value: 17.2 mgKOH / g), product name: BYKJET-9152 (amine value: 27.3 mgKOH / g); and AJISPER series manufactured by Ajinomoto Fine-Techno Co., Ltd., such as product name: AJISPERPB821 (amine value: 11.2 mgKOH / g), product name: AJISPER PB822 (amine value: 18.2 mgKOH / g), product name: AJISPERPB881 (amine value: 17.4 mgKOH / g).

[0299] The amine value of the dispersant (F1) is preferably 10 mgKOH / g or more, more preferably 10 mgKOH / g or more and 30 mgKOH / g or less, and further preferably 15 mgKOH / g or more and 30 mgKOH / g or less. In addition, the dispersant (F1) preferably does not have a phosphate group. In the case where the dispersant (F1) has a phosphate group, the acid value from the phosphate group is preferably less than the value of the amine value. In this case, the dispersant (F1) can disperse the hygroscopic agent (C) particularly well, can particularly improve the storage stability of the composition (X), can particularly improve the transparency of the cured product, and can particularly improve the adhesion between the cured product and silicon nitride and silicon oxide. Among the components that the dispersant (F1) can contain, examples of dispersants having an amino group and not having a phosphate group include DISPERBYK-108 manufactured by BYK-Chemie. Examples of the dispersant having an amino group and a phosphoric acid group and having an acid value derived from the phosphoric acid group that is less than or equal to the amine value include DISPERBYK-2013 manufactured by BYK-Chemie and DISPERBYK-180 manufactured by BYK-Chemie.

[0300] The acidic polar functional group in the dispersant (F2) having an acidic polar functional group is, for example, a carboxyl group. The dispersant (F2) contains, for example, DISPERBYK-P105 manufactured by BYK-Chemie.

[0301] The amount of dispersant (D) relative to 100 parts by mass of hygroscopic agent (C) is preferably 5 parts by mass or more and 60 parts by mass or less. If the amount of dispersant (D) is 5 parts by mass or more, the advantages of dispersant (D) can be particularly exerted. If the amount of dispersant (D) is 60 parts by mass or less, the adhesion between the cured product and silicon nitride and silicon oxide can be further improved. The amount of dispersant (D) is more preferably 15 parts by mass or more. The amount of dispersant (D) is more preferably 50 parts by mass or less, further preferably 40 parts by mass or less, and particularly preferably 30 parts by mass or less.

[0302] Preferably, the composition (X) does not contain a solvent. In this case, when a cured product is made from the composition (X), it is not necessary to dry the composition (X) to volatilize the solvent. In addition, the storage stability of the composition (X) is further improved. When the composition (X) contains a solvent, the content of the solvent (the percentage of the solvent relative to the entire composition (X)) is preferably 1% by mass or less. The content of the solvent is more preferably 0.5% by mass or less, further preferably 0.3% by mass or less, and particularly preferably 0.1% by mass or less. It is particularly preferred that the composition (X) does not contain a solvent, or contains only a solvent that is inevitably mixed in.

[0303] Composition (X) can be prepared by mixing the above components. It is preferred that composition (X) is liquid at 25°C.

[0304] 3. Method for manufacturing sealing material and method for manufacturing light-emitting device

[0305] A method for producing the sealing material 5 and a method for producing the light-emitting device 1 using the composition (X) will be described.

[0306] In this embodiment, it is preferred that the composition (X) is formed by inkjet method and then irradiated with ultraviolet rays to cure the composition (X) to produce the sealing material 5. In this embodiment, the composition (X) can be formed by applying the inkjet method.

[0307] When the composition (X) is applied by an inkjet method, if the composition (X) has a sufficiently low viscosity at room temperature, for example, a viscosity of 30 mPa·s or less, particularly 15 mPa·s or less at 25° C., the composition (X) can be applied by an inkjet method to form a film without heating the composition (X).

[0308] When the composition (X) has a property of decreasing viscosity by heating, the composition (X) can be formed by applying the composition (X) by an inkjet method after heating the composition (X). When the viscosity of the composition (X) at 40°C is 30 mPa·s or less, particularly 15 mPa·s or less, the viscosity of the composition (X) can be decreased by simply heating the composition (X), and the composition (X) with decreased viscosity can be ejected by an inkjet method. The heating temperature of the composition (X) is, for example, 20°C or more and 50°C or less.

[0309] When the coating film obtained by shaping the composition (X) is irradiated with light to cure it, the light irradiated to the coating film is, for example, ultraviolet rays. Ultraviolet rays refer to light with a wavelength in the range of more than 200nm and less than 410nm. The wavelength of the light irradiated to the coating film is preferably in the range of more than 350nm and less than 410nm. As one of the representative examples of the light irradiated to the coating film, light with a wavelength of 365nm can be cited. It should be noted that the wavelength of the light irradiated to the coating film is not limited to the above description as long as it can cure the coating film.

[0310] The irradiation intensity of the light irradiated to the coating film is preferably 20 mW / m 2 Above and 20W / cm 2 It should be noted that the irradiation intensity of light is not limited to the above description as long as the coating film can be cured.

[0311] The shape of the portion irradiated with light when irradiating the coating film may be an area type having a certain degree of area, or may be a linear type. In the case of a linear type, the coating film can be irradiated with light as a whole by moving the coating film relative to the light source, or by moving the light source relative to the coating film. In this case, it is easy to adjust the time for irradiating the coating film with light, and by adjusting the time, it is easy to adjust the accumulated light amount.

[0312] More specifically, for example, a support substrate 2 is first prepared. On one side of the support substrate 2, a partition wall is formed by photolithography using, for example, a photosensitive resin material. Next, a plurality of light-emitting elements 4 are provided on one side of the support substrate 2. The light-emitting elements 4 can be formed by an appropriate method such as a vapor deposition method or a coating method. It is particularly preferred to form the light-emitting elements 4 by a coating method such as an inkjet method. Thus, an element array 9 is formed on the support substrate 2.

[0313] Next, the first passivation layer 61 is provided on the element array 9. For example, the first passivation layer 61 can be formed by a vapor deposition method such as a plasma CVD method.

[0314] Next, the composition (X) is formed on the first passivation layer 61 by, for example, an inkjet method to form a coating film. If the inkjet method is applied to either the formation of the light-emitting element 4 or the coating of the composition (X), the manufacturing efficiency of the light-emitting device 1 can be particularly improved. Next, the coating film is cured by irradiating ultraviolet rays to form a sealing material 5. The thickness of the sealing material 5 is, for example, 5 μm or more and 50 μm or less.

[0315] The thickness of the sealing material 5 is also preferably 4 μm or more and 50 μm or less, and more preferably 4 μm or more and 15 μm or less. As described above, in the present embodiment, it is easy to form small droplets of the composition (X) at a high density by the inkjet method, so it is easy to realize a thin sealing material 5 of 4 μm or more and 15 μm or less. If the sealing material 5 is made thinner in this way, it is not easy for the sealing material 5 to generate tensile stress and compressive stress in the light-emitting device 1. Therefore, it is easy to realize a flexible light-emitting device 1.

[0316] Next, the second passivation layer 62 is provided on the sealing material 5. The second passivation layer 62 can be formed by, for example, a vapor deposition method such as a plasma CVD method.

[0317] Next, after an ultraviolet curable resin material is provided on one surface of the support substrate 2 so as to cover the second passivation layer 62, the transparent substrate 3 is stacked on the resin material. The transparent substrate 3 is, for example, a glass substrate or a transparent resin substrate.

[0318] Next, ultraviolet rays are irradiated from the outside toward the transparent substrate 3. The ultraviolet rays pass through the transparent substrate 3 and reach the ultraviolet curable resin material. As a result, the ultraviolet curable resin material is cured, and the second sealing material 52 is produced.

[0319] In the present embodiment, as described above, even if the composition (X) is applied by an inkjet method, satellite drops are not easy to be generated, so the sealing material 5 can be made by the composition (X) with high precision. The amount of droplets of the composition (X) ejected by the inkjet method is, for example, more than 7pl and less than 10pl, but it can also be less than it. In the present embodiment, even if the droplets are miniaturized, satellite drops can not be easily generated, so the amount of droplets can also be made less than 7pl. In particular, even in the case where the droplets of the composition (X) ejected by the inkjet method are small, for example, the droplets are more than 2pl and less than 7pl, or more than 2pl and less than 5pl, satellite drops are not easy to be generated. As described above, in the case where the acrylic compound (X) contains a compound having an isobornyl skeleton, it is particularly easy to miniaturize the droplets. Therefore, even if the droplets of the composition (X) ejected by the inkjet method are reduced in order to make a thin sealing material 5 such as a thickness of more than 2μm and less than 8μm, the sealing material 5 can be made by the composition (X) with high precision. That is, by forming small droplets at a high density, it is easy to achieve a thinner sealant 5. It should be noted that in this embodiment, the amount of droplets and the thickness of the sealant 5 are not limited to the above range. That is, the amount of droplets can be more than 5 pl, and the thickness of the sealant 5 can be greater than 8 μm.

[0320] In addition, as described above, the sealing material 5 composed of the cured product of the composition (X) can have good heat resistance. Therefore, when the passivation layer 6 (second passivation layer 62) is formed by a deposition method such as a plasma CVD method by overlapping the sealing material 5, the sealing material 5 is not easily degraded even if the temperature of the sealing material 5 rises. In addition, even if the temperature of the light-emitting device 1 rises when the light-emitting device 1 is used, the sealing material 5 is not easily degraded.

[0321] It should be noted that the use of the composition (X) of the present embodiment is not limited to the preparation of the sealing material 5 for the light-emitting element 4. The composition (X) can be used to prepare various substances formed by an inkjet method. For example, a phosphor can be contained in the composition (X), and a color resist in a color filter can be prepared by the composition (X). In this case, it is easy to prepare the color resist in the color filter with high density and high precision. The color filter can be provided in a display device such as an organic EL display or a micro LED display.

[0322] Example

[0323] Hereinafter, specific examples of the present invention will be presented, but the present invention is not limited to the following examples.

[0324] 1. Preparation of the composition

[0325] The compositions of Examples and Comparative Examples were prepared by mixing the components shown in the "Composition" column of the following table.

[0326] The details of the components shown in the table are as follows. The viscosity of the following components was measured using a rheometer (manufactured by Anton Paar Japan, model DHR-2) at a temperature of 25°C and a shear rate of 1000 s. -1 The value measured under the conditions of .

[0327] In addition, the glass transition temperature of the acrylic compound described below was measured by the following method. An acrylic compound and a photopolymerization initiator (Irgacure 184) in an amount of 5% by mass relative to the acrylic compound were mixed to obtain a mixture. The mixture was formed into a film-like body and a high-pressure mercury lamp was used to illuminate the film at a maximum illumination of 200 mW / cm 2 , cumulative light intensity 1500mJ / cm 2 The acrylic compound was polymerized by irradiating with ultraviolet rays under conditions of , and a film with a thickness of 10 μm was prepared. The temperature at which tan δ showed a maximum when differential scanning calorimetry of the film was performed using a viscoelasticity spectrometer "DMS100" manufactured by Seiko Instruments Co., Ltd. at a heating rate of 5°C / min was taken as the glass transition temperature of the acrylic compound.

[0328] (1) Acrylic compounds

[0329] Tricyclodecane dimethanol diacrylate: manufactured by Nippon Kayaku, product number R684, viscosity 110 mPa·s (25°C), glass transition temperature 187°C.

[0330] Bisphenol A polyethoxy diacrylate: manufactured by Nippon Kayaku, product number R551, viscosity 800 mPa·s (25°C), glass transition temperature 60°C.

[0331] Bisphenol F polyethoxy diacrylate: manufactured by Nippon Kayaku, product number R712, viscosity 330 mPa·s (25°C), glass transition temperature 45°C.

[0332] Trimethylolpropane triacrylate: manufactured by Sartomer, product number SR351S, viscosity 106 mPa·s (25° C.), glass transition temperature 62° C.

[0333] Pentaerythritol tetraacrylate: manufactured by Shin-Nakamura Chemical Industry Co., Ltd., viscosity 200 mPa·s (40°C), glass transition temperature 103°C.

[0334] Isobornyl acrylate: manufactured by Osaka Organic Chemical Industry Co., Ltd., product number IBXA, viscosity 8 mPa·s (25°C), glass transition temperature 97°C.

[0335] Dicyclopentanyl acrylate: manufactured by Hitachi Chemical, product number FA-513AS, viscosity 13 mPa·s (25°C), glass transition temperature 120°C.

[0336] · 4-tert-Butylcyclohexyl acrylate: a compound represented by formula (110), having a viscosity of 7 mPa·s (25° C.) and a glass transition temperature of 77° C.

[0337] · 3,3,5-Trimethylcyclohexyl acrylate: a compound represented by formula (120), manufactured by Osaka Organic Chemical Industry Co., Ltd., product name: Viscoat #196, viscosity: 3 mPa·s (25° C.), glass transition temperature: 52° C.

[0338] Neopentyl glycol diacrylate: manufactured by Sartomer, product number SR247, viscosity 6 mPa·s (25° C.), glass transition temperature 117° C.

[0339] 1,6-Hexanediol diacrylate: manufactured by Sartomer, product number SR238B, viscosity 7 mPa·s (25° C.), glass transition temperature 105° C.

[0340] Polyethylene glycol 200 dimethacrylate: manufactured by Shin-Nakamura Chemical Industry Co., Ltd., viscosity 14 mPa·s (25°C), glass transition temperature 41°C.

[0341] Polyethylene glycol 200 diacrylate: manufactured by Osaka Organic Chemical, viscosity 17 mPa·s (25°C), glass transition temperature 41°C.

[0342] (2) Cationic polymerizable compounds

[0343] CELLOXIDE 8010: manufactured by Daicel, product name CELLOXIDE 8010, a compound represented by formula (1a), specific gravity 1.11, viscosity 60 mPa·s, refractive index 1.5071.

[0344] ·X-40-2732: manufactured by Shin-Etsu Chemical, product number X-40-2732, a compound represented by formula (10a) (a mixture of n=1 to 4, R=C2H4), specific gravity 0.996, viscosity 20 mPa·s, refractive index 1.4512.

[0345] OXT-221: manufactured by Toa Gosei Co., Ltd., product number OXT-221, a compound represented by formula (3), specific gravity 0.998, viscosity 10 mPa·s, refractive index 1.4538.

[0346] ·3-Allyloxymethyl-3-ethyloxetane: a compound represented by formula (16), boiling point 200°C, specific gravity 0.933, viscosity 2 mPa·s, refractive index 1.4445.

[0347] (3) Photoradical polymerization initiator

[0348] Irgacure 184: 1-Hydroxy-cyclohexyl-phenyl-ketone, manufactured by BASF, product number Irgacure 184.

[0349] Irgacure TPO: 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, BASF, product number Irgacure TPO.

[0350] (4) Cationic curing catalyst

[0351] ·DTS-200: Made by MIDORI Chemical, product number DTS-200.

[0352] (5-1) Zeolite particles 1

[0353] The zeolite particles 1 were produced by the following method, and had a D50 of 20 nm, a D90 of 50 nm, and a pH of 11.

[0354] As a starting material, zeolite powder of type 4A zeolite-sodium ion having an average particle size of 5 μm was prepared, and 100 g of the zeolite powder and 100 g of ion-exchanged water were mixed to prepare a slurry.

[0355] After adding 400 g of zirconia beads with a particle size of 100 μm to the slurry, the zeolite powder in the slurry was pulverized for 3 hours using a bead mill to reduce the average particle size of the zeolite powder to 120 nm. The slurry flow rate at this time was 10 kg / h and the slurry viscosity was 10 mPa·s.

[0356] Next, the zirconia beads with a particle size of 100 μm were removed from the slurry, and 400 g of zirconia beads with a particle size of 50 μm were added instead, and the zeolite powder in the slurry was crushed for 1 hour using a bead mill, so that the average particle size of the zeolite powder was 70 nm. The slurry flow rate at this time was 10 kg / h, and the slurry viscosity was 6 mPa·s.

[0357] Next, zirconia beads with a particle size of 50 μm were removed from the slurry, and 450 g of zirconia beads with a particle size of 30 μm were added instead, and the zeolite powder in the slurry was crushed for 1 hour using a bead mill, so that the average particle size of the zeolite powder was 20 nm. The slurry flow rate at this time was 10 kg / h, and the slurry viscosity was 4 mPa·s.

[0358] Next, the slurry was left at 180° C. for 2 to 3 hours to obtain finely pulverized zeolite powder. The zeolite powder was crushed in a mortar and then passed through a sieve to adjust the particle size, thereby obtaining zeolite particles 1 .

[0359] The pH of the zeolite particles was measured by the following method. After adding 0.05 g of zeolite particles and 99.95 g of ion exchange water to a polyethylene bottle, the bottle was placed in a thermostatic bath and heated at 90° C. for 24 hours. Next, the pH of the supernatant of the liquid in the bottle was measured using a small pH meter <LAQUAtwin> B-711 manufactured by Horiba, Ltd.

[0360] (5-2) Zeolite particles 2

[0361] The zeolite particles 2 were produced by the following method, and had a D50 of 60 nm, a D90 of 110 nm, and a pH of 11.

[0362] Zeolite powder of type 4A-sodium with an average particle size of 5 μm was prepared as a starting material, and 100 g of the zeolite powder and 100 g of ion exchange water were mixed to prepare a slurry. The zeolite powder in the slurry was pulverized by the method based on the case of zeolite particles 1 to an average particle size of 60 nm.

[0363] Next, the slurry was left at 180° C. for 2 to 3 hours to obtain finely pulverized zeolite powder. The zeolite powder was crushed in a mortar and then passed through a sieve to adjust the particle size, thereby obtaining zeolite particles 2 .

[0364] (5-3) Zeolite particles 3

[0365] The zeolite particles 3 were produced by the following method, and had a D50 of 150 nm, a D90 of 250 nm, and a pH of 11.

[0366] Zeolite powder of type 4A-sodium with an average particle size of 5 μm was prepared as a starting material, and 100 g of the zeolite powder and 100 g of ion exchange water were mixed to prepare a slurry. The zeolite powder in the slurry was pulverized by the method based on the case of zeolite particles 1 to an average particle size of 150 nm.

[0367] Next, the slurry was left at 180° C. for 2 to 3 hours to obtain finely pulverized zeolite powder. The zeolite powder was crushed in a mortar and then passed through a sieve to adjust the particle size, thereby obtaining zeolite particles 3 .

[0368] (5-4) Zeolite particles 4

[0369] The zeolite particles 4 were produced by the following method, and had a D50 of 60 nm, a D90 of 110 nm, and a pH of 11.

[0370] Zeolite powder of type 4A-sodium with an average particle size of 5 μm was prepared as a starting material, and 100 g of the zeolite powder and 100 g of ion exchange water were mixed to prepare a slurry. The zeolite powder in the slurry was pulverized by the method based on the case of zeolite particles 1 to an average particle size of 60 nm.

[0371] The zeolite powder in the treated slurry is subjected to hydrothermal synthesis treatment by the following method. 50 g of the slurry is placed in a fluororesin container, and the fluororesin container is placed in a stainless steel (SUS316) container of an autoclave. The stainless steel container has a capacity of 100 cc, a heat-resistant temperature of 200°C, a pressure resistance of 50 MPa, and a closed structure sealed by a lid with a safety valve. The stainless steel container is placed in a dryer and sealed, and heated at 180°C for 24 hours. Next, the stainless steel container is taken out of the dryer and placed in water at room temperature for rapid cooling.

[0372] The fluororesin container was taken out from the stainless steel container, placed on a shallow tray, and left at 180°C for 2 to 3 hours to dry the slurry in the fluororesin container. Thus, finely crushed zeolite powder was obtained. The zeolite powder was taken out from the fluororesin container, crushed in a mortar, and passed through a sieve to adjust the particle size, thereby obtaining zeolite particles 4.

[0373] (5-5) Zeolite particles 5

[0374] The zeolite particles 5 are powder products not subjected to surface treatment and are product number ZEOLUM 4A manufactured by Tosoh Corporation. They are 100 mesh-passing products, have a D50 of 13 μm, a D90 of 30 μm, and a pH of 10.

[0375] (6) Dispersant

[0376] Solsperse 32000: A comb-shaped resin dispersant of fatty acid amine with polyethyleneimine as the main skeleton, amine value 31 mgKOH / g, acid value 15 mgKOH / g, boiling point above 200°C, manufactured by Lubrizol, product name Solsperse 32000.

[0377] 2. Evaluation test

[0378] The following evaluation tests were carried out on Examples and Comparative Examples, and the results are shown in the table.

[0379] (1) Transmittance

[0380] The composition was applied to form a coating film, and an LED-UV irradiator (peak wavelength 365 nm) manufactured by Panasonic Electric Works Co., Ltd. was used at a power of about 30 mW / cm 2 The coating film was irradiated with ultraviolet rays for 20 seconds under the conditions of , and photocured to prepare a film having a thickness of 10 μm. The total light transmittance of the film was measured in accordance with JIS K7361-1.

[0381] (2) Viscosity

[0382] A rheometer (Anton Paar Japan, Model DHR-2) was used at a temperature of 25°C and a shear rate of 1000 s. -1 The viscosity of the composition was measured under the conditions of .

[0383] (3) Maximum peak value of the characteristic curve

[0384] The composition was measured using a capillary fracture mode elongation strain rheometer under the conditions of a temperature of 25°C, a diameter of 4 mm for the upper plate and the lower plate, an initial gap of 1 mm between the upper plate and the lower plate, a pulling distance (displacement) of 3 mm for the upper plate, a pulling time of 30 milliseconds for the upper plate, and a diameter measurement rate of 30,000 Hz (30,000 times / second), to obtain a diameter-time curve at 25°C. The characteristic curve was obtained by performing data conversion on the diameter-time curve at 25°C. The same composition was measured three times to obtain three characteristic curves. The average value of the maximum peak values ​​of these characteristic curves was calculated and used as the maximum peak value of the characteristic curve of the composition. The characteristic curve in the case of Example 1 is shown in Figure 3 The characteristic curve of Comparative Example 1 is shown in Figure 4 In Comparative Example 4, since precipitation of zeolite particles occurred, the characteristic curve had a large deviation, and therefore no effective value was obtained as the maximum peak.

[0385] (4) Ratio of maximum peak to viscosity

[0386] The maximum peak value of the characteristic curve of the composition obtained in (3) above was divided by the value of the viscosity obtained in (2) above, thereby calculating the ratio of the maximum peak value to the viscosity.

[0387] (5) Glass transition temperature of the cured product

[0388] The composition was placed in an ink cartridge of an inkjet printer (Microjet, "NanoPrinter 300"), and the composition was ejected from the nozzle of the inkjet printer while the composition was maintained at 25°C to prepare a coating film. The coating film was left to stand in an argon atmosphere (dew point temperature -70°C) at 20°C for 24 hours. Next, an LED-UV irradiator (peak wavelength 365nm) manufactured by Panasonic Electric Works was used at about 30mW / cm 2 The coating film was irradiated with ultraviolet rays for 20 seconds under the conditions of , and photocured, thereby producing a film with a thickness of 10 μm.

[0389] The glass transition temperature of the film obtained above was measured using a viscoelasticity spectrometer "DMS100" manufactured by Seiko Instruments Co., Ltd. In this case, a dynamic viscoelasticity measurement (DMA) was performed using a tensile module at a frequency of 10 Hz, and the temperature at which tan δ showed a maximum when the temperature was raised from room temperature to 230°C at a heating rate of 5°C / min was taken as the glass transition temperature.

[0390] (6) Inkjet properties

[0391] (6-1) Evaluation 1

[0392] As an inkjet printer, a model MH2420 manufactured by RICOH was used, and the composition was placed in the ink cartridge of the inkjet printer. When the composition was maintained at 25°C and when the composition was heated to 40°C, droplets of the composition were ejected from the nozzle of the inkjet printer, respectively. The minimum amount of droplets at this time was 7.0 pl. The droplets were ejected from the nozzle using a high-speed camera to confirm whether the droplets were separated and satellite droplets were generated. As a result, the situation where no satellite droplets were generated was evaluated as "good", and the situation where satellite droplets were generated was evaluated as "bad". In addition, based on the shooting results of the high-speed camera, the speed of the droplets at the maximum voltage that was ejected without generating satellite droplets was measured.

[0393] (6-2) Evaluation 2

[0394] The ink jetting properties were evaluated by the same method as in the above "(6-1) Evaluation 1" except that a RICOH model MH5420 was used as the ink jet printer. The minimum amount of droplets at this time was 2.5 pl.

[0395] (7) Contractility

[0396] The volume and mass of the composition were measured, and the specific gravity of the composition was calculated based on the results. In addition, the composition was applied to form a coating film, and an LED-UV irradiator (peak wavelength 365 nm) manufactured by Panasonic Electric Works Co., Ltd. was used at about 30 mW / cm 2The coating was irradiated with ultraviolet light for 20 seconds under the conditions of , thereby photocuring it to produce a film with a thickness of 200 μm. The specific gravity of the sample cut out from the film was measured using a specific gravity bottle. Based on these results, the shrinkage rate was calculated using the following calculation formula.

[0397] Shrinkage (%) = {1-(specific gravity of composition)} / (specific gravity of sample) × 100

[0398] As a result, the case where the shrinkage rate was 2% or more and less than 5% was evaluated as "A", the case where the shrinkage rate was 5% or more and less than 10% was evaluated as "B", and the case where the shrinkage rate was 10% or more was evaluated as "C".

[0399] (8) Adhesion

[0400] A 100 nm thick silicon nitride film (refractive index 1.81) was formed on the surface of a quartz glass sheet (size 50 mm×25 mm×1 mm) by plasma CVD. The composition was applied on the silicon nitride film to form a 50 μm thick coating film. Thus, a first test piece was prepared.

[0401] On the surface of another quartz glass piece (size: 76 mm×52 mm×1 mm), a 100 nm thick silicon nitride film (refractive index: 1.81) was formed by plasma CVD method, thereby preparing a second test piece.

[0402] The silicon nitride film of the second test piece was overlapped on the coating film of the first test piece so that the size of the contact area between the two pieces was 25 mm × 25 mm. Next, an LED-UV irradiator (peak wavelength 365 nm) manufactured by Panasonic Electric Works was used at a power of about 100 mW / cm 2 The coating film was cured by irradiating it with ultraviolet rays for 30 seconds under the conditions of .

[0403] Next, a tensile shear test (tensile speed 5 mm / min) was performed in accordance with JIS-K-6850 to evaluate the adhesion strength between the two quartz glass sheets.

[0404] [Table 1]

[0405]

[0406] [Table 2]

[0407]

Claims

1. A UV-curable resin composition, characterized in that The maximum peak value of the apparent elongation viscosity-Hencky strain curve at 25°C is less than 350 mPa·s. The ratio of the maximum peak value to the viscosity at 25°C is 20 or less, It has a property of becoming a cured product having a glass transition temperature of 80° C. or higher by curing. 2 . The ultraviolet curable resin composition according to claim 1 , comprising an acrylic compound (A) and a photoradical polymerization initiator (B).

3. The ultraviolet curable resin composition according to claim 2, wherein The acrylic compound (A) contains a polyfunctional acrylic compound (A1) having two or more (meth)acryloyl groups in one molecule.

4. The ultraviolet curable resin composition according to claim 2 or 3, wherein The acrylic compound (A) contains a component (a), and the component (a) contains at least one compound having a viscosity of 20 mPa·s or less at 25° C.

5. The ultraviolet curable resin composition according to claim 4, wherein The component (a) contains a compound having a glass transition temperature of 80° C. or higher.

6. The ultraviolet curable resin composition according to claim 4, wherein The component (a) contains at least one compound selected from the group consisting of isobornyl acrylate, neopentyl glycol diacrylate, 1,6-hexanediol diacrylate, polyethylene glycol 200 dimethacrylate and polyethylene glycol 200 diacrylate.

7. The ultraviolet curable resin composition according to claim 4, wherein The ratio of the component (a) to the total amount of the acrylic compound (A) is 50% by mass or more and 100% by mass or less.

8. The ultraviolet curable resin composition according to claim 2 or 3, wherein The acrylic compound (A) contains a component (b), wherein the component (b) contains a compound having at least one skeleton selected from a dicyclopentadiene skeleton, a dicyclopentyl skeleton, a dicyclopentenyl skeleton, and a bisphenol skeleton. The ratio of the component (b) to the total amount of the acrylic compound (A) is 5% by mass or more and 50% by mass or less. 9 . The ultraviolet curable resin composition according to claim 1 , further comprising a moisture absorbent (C).

10. The ultraviolet curable resin composition according to claim 9, wherein The moisture absorbent (C) contains zeolite particles. 11 . The ultraviolet curable resin composition according to claim 9 , comprising a dispersant (D).

12. The ultraviolet curable resin composition according to claim 11, wherein The boiling point of the dispersant (D) is 200° C. or higher.

13. The ultraviolet curable resin composition according to claim 11, wherein The amount of the dispersant (D) is 5 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the moisture absorbent (C). 14 . The ultraviolet curable resin composition according to claim 1 , which contains no solvent or contains a solvent in an amount of 1% by mass or less.

15. The ultraviolet curable resin composition according to any one of claims 1 to 3, wherein The light transmittance of the cured product is above 90%. 16 . The ultraviolet curable resin composition according to claim 1 , which has a viscosity at 25° C. of 1 mPa·s or more and 15 mPa·s or less. 17 . The ultraviolet curable resin composition according to claim 1 , wherein the viscosity at 40° C. is 1 mPa·s or more and 15 mPa·s or less. 18 . The ultraviolet curable resin composition according to claim 1 , which is used for producing a sealing material for a light emitting element. 19 . The ultraviolet curable resin composition according to claim 1 , which is molded by an inkjet method.

20. A method for manufacturing a light emitting device, characterized in that: A method for manufacturing a light-emitting device having a light-emitting element and a sealing material covering the light-emitting element, comprising: The ultraviolet curable resin composition according to any one of claims 1 to 19 is molded by an inkjet method, and then irradiated with ultraviolet rays to cure the ultraviolet curable resin composition, thereby producing a sealing material.

21. A light emitting device, characterized in that: A light emitting element and a sealing material covering the light emitting element are provided, wherein the sealing material is formed of a cured product of the ultraviolet curable resin composition according to any one of claims 1 to 19.

Citation Information

Patent Citations

  • New o-acyloxime photopolymerization initiator

    JP2000080068A

  • Photoinitiator of oxime ester

    JP2001233842A

  • Oxime ester photopolymerization initiator

    JP2010527338A

  • Oxime ester photopolymerization initiator

    JP2010527339A

  • Photosensitive resin composition for photospacer and photospacer using the same

    JP2013041153A